Glass panes and windows
Patent Information
- Application Number
- JP2023202778
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-07-20
- Filing Date
- 2023-11-30
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2038-04-27
AI Technical Summary
【0008】 本発明のガラス板および窓によって、高周波数帯の電波を利用する電波利用機器を、自動車や建物の室内でも支障なく使用することが可能になる。
Smart Images

Figure 0007643505000029 
Figure 0007643505000030 
Figure 0007643505000031
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass sheet used as a window material for vehicles, buildings, etc. [Background technology]
[0002] It has become commonplace to use devices that use radio waves, such as radars and mobile phones, in vehicles including automobiles and indoors in buildings. In particular, in recent years, there has been active development of devices that use radio waves in the high frequency band (microwaves to millimeter waves), more specifically in the gigahertz frequency band, for example, in the 3 to 300 GHz range.
[0003] Glass used as a window material for automobiles and buildings is described, for example, in Patent Document 1. Patent Document 1 discloses that it is possible to obtain glass that has high visible light transmittance, high ultraviolet and solar radiation shielding performance, and is visually pleasing. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2002-348143 Summary of the Invention [Problem to be solved by the invention]
[0005] However, there have been no examples of glass for window materials that have been developed with particular consideration given to suitability for use in devices that utilize radio waves.
[0006] An object of the present invention is to provide a glass sheet for window materials and a window that are unlikely to interfere with radio wave transmission and reception by radio wave utilizing devices when the devices are used in an environment where window glass is present. [Means for solving the problem]
[0007] The present invention provides a glass plate having a radio wave transmittance of 20% or more at a frequency of 100 GHz when converted into a plate having a thickness of 18 mm, a window including the glass plate, and a wireless communication device including the glass plate. Effect of the Invention
[0008] The glass plate and window of the present invention make it possible to use radio wave utilizing devices that utilize radio waves in the high frequency band without any problems even inside a car or a building. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a schematic diagram showing an outline of conditions for determining radio wave transmittance. [Figure 2A] 1 is a graph showing the electric field strength ratios of the glass plates of Comparative Example 1 and Examples 1 to 6 at a thickness of 18 mm. [Figure 2B] 1 is a graph showing the electric field strength ratios of the glass plates of Comparative Example 1 and Examples 7 to 12 at a thickness of 18 mm. [Figure 2C] 1 is a graph showing the electric field strength ratios of the glass plates of Comparative Example 1 and Examples 13 to 17 at a thickness of 18 mm. [Figure 2D] 1 is a graph showing the electric field strength ratios of the glass plates of Comparative Example 1 and Examples 18 to 20 at a thickness of 18 mm. [Figure 3A] 1 is a graph showing approximate transmittances of Comparative Example 1 and Examples 1 to 6. [Figure 3B] 1 is a graph showing approximate transmittances of Comparative Example 1 and Examples 7 to 12. [Figure 3C] 1 is a graph showing approximate transmittances of Comparative Example 1 and Examples 13 to 17. [Figure 3D] 1 is a graph showing approximate transmittances of Comparative Example 1 and Examples 18 to 20. [Figure 4] 1 is a graph showing measured values of radio wave transmission amount for the laminated glass of Comparative Example 1 and calculated values of radio wave transmission amount obtained by exponential approximation. [Diagram 5]1 is a graph showing the measured values of radio wave transmission for the laminated glasses of Comparative Example 1, Example 3, Example 4, Example 11, and Example 25 and the calculated values of radio wave transmission obtained by exponential approximation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Unless otherwise stated, the definitions of terms provided below apply throughout the specification, drawings, and claims. The symbol "~" indicating a range of values means that the values before and after it are included as the lower and upper limits, respectively. When glass is "substantially free" of a certain component, it means that the component is not actively added, except when it is inevitably mixed in as an impurity. The content of each component in glass is expressed as a mole percentage based on the oxide.
[0011] In this specification, the "radio wave transmittance" of a glass plate is determined as follows. As shown in FIG. 1, a perfect conductor frame 10 having an infinite area and a finite thickness is placed on a 90 mm square (8100 mm 2 ) square opening 20. A plane wave with an electric field strength of 1 V / m is incident perpendicularly to the opening from a wave source 30 located 60 mm away from the opening in the vertical direction, so that the wave front is parallel to the opening and the polarization direction is parallel to one side of the opening. Then, the electric field strength is observed at a point (observation point 40) located 300 mm away from the center point of the opening in the vertical direction on the opposite side of the opening from the wave source. Here, the electric field strength ratio of the glass plate is obtained by dividing the electric field strength observed when a glass plate sample of the same shape and area as the opening 20 is fitted in the opening 20 by the electric field strength observed when the glass plate sample is not fitted (i.e., when the glass plate sample is replaced with an air mass of the corresponding thickness). This electric field strength ratio can be obtained by performing a simulation using the above-mentioned conditions with an electromagnetic field simulator (CST Microwave Studio 2016). The electric field intensity ratio is the ratio of the electric field intensity observed through the glass plate sample to the electric field intensity observed through the air under the above conditions, and is a dimensionless number unless otherwise indicated in units, but may be expressed as a percentage (%). The electric field intensity ratio can be determined according to the thickness, dielectric constant, and dielectric loss of the glass plate, as well as the frequency of the incident wave. Methods for measuring the dielectric constant and dielectric loss of a glass plate sample are known to those skilled in the art, and are measured, for example, by a cavity resonance method.
[0012] As used herein, unless otherwise specified, the following terms have the following meanings: An aperture is a square opening in the frame of a perfect conductor with an infinite area. When observing the transmittance of radio waves through a glass plate or the electric field strength after transmission, a glass plate sample of the same shape and area as the aperture is fitted into the aperture. The wavefront of the plane wave is parallel to the aperture plane, the polarization direction of the plane wave is parallel to one side of the aperture, and the plane wave is incident perpendicular to the aperture. Descriptions of the distance from the aperture refer to the distance along a perpendicular line from the aperture plane. Descriptions of an observation point a certain distance away from the aperture refer to a point that is that distance away from the aperture plane along a perpendicular line from the center point of the aperture. The wave source and observation point are located on opposite sides of the aperture. The thickness of the glass plate is mm, and the area of the opening is mm 2 The wavelength of radio waves is expressed in mm, the frequency in GHz, and the electric field strength in V / m.
[0013] The glass plate according to the present invention has a radio wave transmittance of 20% or more at a frequency of 100 GHz, calculated based on a thickness of 18 mm. This makes the glass plate less likely to be a barrier to transmission and reception by radio wave-using devices such as radars and mobile phones. In this specification, unless otherwise specified, the radio wave transmittance is obtained by performing exponential approximation as described below. This radio wave transmittance is preferably 21% or more, more preferably 22% or more, more preferably 25% or more, more preferably 29% or more, more preferably 33% or more, more preferably 37% or more, more preferably 40% or more, even more preferably 43% or more, particularly preferably 45% or more, even more preferably 48% or more, and most preferably 50% or more. The conversion of radio wave transmittance to thickness can be performed analytically, for example, using the plane electromagnetic wave propagation equation shown in "Chapter 2: Transmission of Electromagnetic Waves" in Introduction to Electromagnetic Wave Guidance Theory (written by Masahiro Hashimoto, published by Nikkan Kogyo Shimbun, Ltd.). The glass plate according to the present invention preferably has a radio wave transmittance of 23% or more at a frequency of 80 GHz, calculated based on a thickness of 18 mm. This makes the glass plate less likely to be a barrier to transmission and reception by radio wave-using devices such as radar and mobile phones. This radio wave transmittance is more preferably 25%, more preferably 26% or more, more preferably 30% or more, more preferably 35% or more, more preferably 40% or more, even more preferably 44% or more, particularly preferably 48% or more, even more preferably 52% or more, and most preferably 54% or more. The glass plate according to the present invention preferably has a radio wave transmittance of 39% or more at a frequency of 28 GHz, calculated based on a thickness of 18 mm. This makes the glass plate less likely to be a barrier to transmission and reception by radio wave-using devices such as radars and mobile phones. This radio wave transmittance is more preferably 40% or more, more preferably 44% or more, more preferably 50% or more, more preferably 56% or more, even more preferably 60% or more, particularly preferably 62% or more, even more preferably 65% or more, and most preferably 68% or more.
[0014] The glass plate according to the present invention preferably has a radio wave transmittance of 84% or less at a frequency of 100 GHz, calculated for a thickness of 18 mm. In order to make the radio wave transmittance exceed 84%, it may be necessary to increase the SiO2 content of the glass excessively. Such glass is difficult to melt, and the forming temperature is also high, making it difficult to manufacture large plates by the float method, fusion method, roll-out method, down-draw method, etc. In addition, if the radio wave transmittance is high, it becomes necessary to add a large amount of B2O3 components, which makes it easier for alkali elements to volatilize during melting and forming, which may lead to deterioration of glass quality, as well as a small average linear expansion coefficient, making physical strengthening difficult. Furthermore, an increase in B2O3 or SiO2 components is likely to cause a decrease in Young's modulus, which may reduce the rigidity of the substrate and make it difficult to ensure strength during use. In addition, in order to increase the radio wave transmittance, it is necessary to reduce the content of alkali elements, which results in a deterioration of solubility and a significant deterioration in viscosity, which is undesirable, and may also be prone to devitrification, causing problems in the manufacture of glass. In such a case, the glass is particularly unsuitable for use as a window glass for automobiles or buildings. Therefore, the radio wave transmittance is more preferably 80% or less, more preferably 70% or less, more preferably 60% or less, more preferably 55% or less, even more preferably 50% or less, particularly preferably 47% or less, even more preferably 45% or less, and most preferably 43% or less. The glass plate according to the present invention preferably has a radio wave transmittance of 84% or less at a frequency of 80 GHz, calculated based on a thickness of 18 mm. In order to make the radio wave transmittance exceed 84%, it may be necessary to excessively increase the SiO2 content of the glass. Such glass is difficult to melt and has a high forming temperature, making it difficult to manufacture large plates by the float method, fusion method, roll-out method, down-draw method, etc. This radio wave transmittance is more preferably 80% or less, more preferably 70% or less, more preferably 61% or less, more preferably 58% or less, even more preferably 55% or less, particularly preferably 52% or less, even more preferably 49% or less, and most preferably 47% or less. The glass plate according to the present invention preferably has a radio wave transmittance of 84% or less at a frequency of 28 GHz, calculated based on a thickness of 18 mm. In order to make the radio wave transmittance exceed 84%, it may be necessary to increase the SiO2 content of the glass excessively. Such glass is difficult to melt and has a high forming temperature, making it difficult to manufacture large plates by the float method, fusion method, roll-out method, down-draw method, etc. The radio wave transmittance is more preferably 82% or less, more preferably 80% or less, more preferably 78% or less, more preferably 76% or less, even more preferably 75% or less, particularly preferably 72% or less, even more preferably 68% or less, and most preferably 64% or less.
[0015] In this specification, λ represents the wavelength of radio waves (unit: mm). In the glass plate according to the present invention, when a plane wave with a frequency of 10 GHz and an electric field strength of 1 V / m is incident on a glass plate with a thickness of 1.2 λ from a wave source 2 λ away from the aperture 20, the electric field strength at an observation point 10 λ away from the aperture is y (V / m), and the aperture area S (mm 2 ) into λ 2 It is preferable that the linear approximation is y>(0.0607×x), where the value obtained by dividing by is x. The observed electric field intensity y, which varies depending on the aperture area, can be determined by performing a simulation using an electromagnetic field simulator (CST Microwave Studio 2016) using each of the above-mentioned conditions. The linear approximation is a linear approximation obtained using the least squares method, as is well known to those skilled in the art. Note that the above description of "when incident on a glass plate with a thickness of 1.2λ" indicates that the glass plate is converted to a thickness of 1.2λ, and the actual thickness of the glass plate of the present invention does not need to be 1.2λ.
[0016] The above linear approximation of the glass plate being y>(0.0607×x) means that the slope of the graph of the linear function obtained by linearly approximating the relationship between x and y obtained from the glass plate is greater than the slope of the graph of y=(0.0607×x). If this linear approximation is y≦(0.0607×x), that is, if the slope is 0.0607 or less, it is likely to hinder the functioning of radio wave-utilizing devices in the high frequency band. The slope of the linear function obtained by the above linear approximation is more preferably 0.0625 or more, and even more preferably 0.0644 or more. There is no problem if this slope is large, but it cannot be more than 0.0879 (the value obtained when observing by placing an air mass instead of a glass plate). The slope of the linear function obtained by the linear approximation is preferably 0.0796 or less. If it is 0.0796 or less, the proportion of SiO2 or B2O3 in the glass can be reduced, making the glass easier to manufacture, and the weather resistance and thermal expansion characteristics of the glass can be adjusted, making it easier to manufacture large glass sheets suitable for making windows for various applications. The slope of the linear function obtained by the linear approximation is more preferably 0.0750 or less, even more preferably 0.0700 or less, even more preferably 0.0690 or less, even more preferably 0.0680, even more preferably 0.0670 or less, even more preferably 0.0665 or less, and most preferably 0.0657 or less.
[0017] The glass plate according to the present invention preferably has an exponential approximation (herein referred to as "exponential approximation at 100 GHz") of y'>exp(-0.081×x'), where y' is the approximate transmittance at a frequency of 100 GHz and x' is the thickness of the glass plate.
[0018] This exponential approximation at 100 GHz is determined as follows. First, for each of the target glass sheets converted to thicknesses of 12 mm, 18 mm, 24 mm, 30 mm, 36 mm, and 40 mm, a curve of the variation of the electric field intensity ratio according to the frequency x'' (GHz) is determined, and an exponential approximation of the relationship between x'' and the electric field intensity ratio (in this specification, this exponential approximation is also referred to as "exponential approximation of the relationship between frequency and radio wave transmittance") is obtained, and this is taken as the radio wave transmittance y''. In other words, y''=[constant 1]×e [定数2]×x’’ The exponential approximation is an exponential approximation obtained by using the least squares method, as is well known to those skilled in the art. For example, for a glass plate (Comparative Example 1) having a thickness of 12 mm, y''=0.7628e -0.003x’’ , and for the same glass plate with a thickness of 18 mm, y''=0.8619e -0.015x’’ The exponential approximation is obtained. This approximation formula was created based on the analysis results at 6 to 20 GHz using an electromagnetic field simulator. Due to the characteristics of the electromagnetic field simulator, the calculation accuracy deteriorates as the frequency moves away from the center frequency of the analysis frequency band, and it is known that the accuracy deteriorates significantly especially in the low frequency band, so it is preferable to apply it to a frequency band of 6 GHz or more. In this calculation, the upper limit frequency for analysis is up to 20 GHz, but since the frequency dependency of the attenuation term is negligibly small, this approximation formula can also be applied to frequencies above 20 GHz. Therefore, in the glass plate of the present invention, in the exponential approximation of the relationship between the frequency and the electric field intensity ratio at frequencies of 6 to 20 GHz converted to a thickness of 18 mm, y''>0.8619e -0.015x’’ It is preferable that y''>0.85e -0.012x’’ , and more preferably y″>0.84e -0.010x’’ , and particularly preferably y″>0.84e -0.09x’’ , more preferably y″>0.84e -0.008x’’ , and most preferably y″>0.84e -0.007x’’ It is. Also, preferably, y''<0.84e -0.0005x’’This allows the content of SiO2 and B2O3 in the glass to be reduced, making the glass easier to manufacture, and also makes it possible to adjust the weather resistance and thermal expansion properties of the glass, making it easier to manufacture large glass sheets suitable for making windows for various applications. More preferably, y''<0.84e -0.001x’’ , and more preferably y″<0.84e -0.003x’ , and particularly preferably y″<0.84e -0.005x’ , more preferably y″<0.8435e -0.006x’’ , and most preferably y''<0.8462e -0.007x’’ It is.
[0019] Next, the transmittance (approximate transmittance) at 100 GHz is calculated based on the exponential approximation equation of the relationship between the frequency and the electric field intensity ratio obtained for each thickness above. Then, the relationship of the approximate transmittance y' according to the thickness x' is obtained for the frequency of 100 GHz, and the above-mentioned "exponential approximation at a frequency of 100 GHz" is obtained by further performing exponential approximation on this relationship. Note that, although the thickness x' is varied as described above for the purpose of the calculation to obtain the exponential approximation, it goes without saying that the specific glass plate of the present invention may have any thickness.
[0020] In general, the electric field strength ratio of radio waves passing through a glass plate varies greatly depending on whether the multiple of the wavelength of the radio waves coincides with the thickness of the glass plate, and is affected in a complex manner by the reflection, refraction, and interference of the radio waves. Therefore, when the frequency is continuously increased, it is observed that the electric field strength ratio rises and falls periodically and in an irregular trajectory (see, for example, Figures 2A to 2D). For this reason, even if the electric field strength ratio actually measured at a certain frequency is larger or smaller, it may not necessarily describe the radio wave transmission characteristics of the glass material in essence. In other words, even if the second glass plate transmits more radio waves than the first glass plate at that specific frequency, the first glass plate may have better radio wave transmission characteristics overall when viewed macroscopically over a wider frequency range (see Figures 2A to 2D). Therefore, the approximation described above is useful, because the approximate formula describes the macroscopic tendency of the radio wave transmission characteristics.
[0021] When the exponential approximation of a certain glass plate at a frequency of 100 GHz is y'>exp(-0.081×x'), it means that the graph of the exponential function obtained by exponentially approximating the relationship between x' and y' obtained from that glass plate is above the graph of y'=exp(-0.081×x'). These graphs are plotted with x' on the horizontal axis and y' on the vertical axis, and when x'=0 (no glass plate thickness), y'=1 (transmittance 100%). If this exponential approximation is y'≦exp(-0.081×x'), it is likely to interfere with transmission and reception of radio wave using devices in the high frequency band. The coefficient of x' in this exponential approximation at a frequency of 100 GHz is more preferably -0.075 or more, even more preferably -0.07 or more, particularly preferably -0.065 or more, even more preferably -0.06 or more, and most preferably -0.055 or more. The coefficient of x' is not a problem if it is large, but is usually -0.01 or less. The coefficient of x' is preferably -0.02 or less. This allows the content of SiO2 and B2O3 components in the glass to be reduced, making the glass easier to manufacture, and also makes it possible to adjust the weather resistance and thermal expansion characteristics of the glass, making it easier to manufacture large glass sheets suitable for making windows for various applications. It is more preferably -0.03 or less, even more preferably -0.035 or less, particularly preferably -0.04 or less, even more preferably -0.045 or less, and most preferably -0.05 or less.
[0022] The glass panes according to the invention preferably have an area of 900 mm 2 That is all. The area of the glass plate is 900 mm 2 If the area is more than 2500 mm, it is possible to ensure the amount of radio wave transmission required for use of radio wave-utilizing devices, and the film can be suitably used for architectural applications, automotive applications, etc. 2 More preferably, it is 10,000 mm 2 More preferably, 90,000 mm 2 More preferably, 180,000 mm 2 More preferably, 360,000 mm 2More than 1,120,000 mm, most preferably 2 That's all. From the perspective of radio wave transmission, there is no particular upper limit on the area, but 2 Larger glass sheets are difficult to manufacture. The area should preferably be 56250000 mm 2 More preferably, it is 25,000,000 mm or less. 2 Less than 9,000,000 mm, particularly preferably 2 Less than 4,000,000 mm, more preferably 2 Below, most preferably 2,160,000 mm 2 The area of the glass plate is 900 mm or less. 2 If it is smaller, applications in architecture, automobiles, etc. may be limited, and the absolute amount of radio waves transmitted through the glass sheet may be small, regardless of the transmittance.
[0023] The glass plate according to the present invention has an A×radio wave transmittance of 0.0225 m 2 %~8400m 2 %, where A is the area of the glass plate (m 2 ) and the radio wave transmittance is the radio wave transmittance (%) at a frequency of 100 GHz converted into a thickness of 18 mm. A x radio wave transmittance is 0.0225m 2 If the thickness is 0.0225m or more, a stronger electric field strength can be obtained than with a conventional glass plate, which is preferable. 2 If the transmittance is less than 0.4m, it becomes difficult to use the window in the high frequency band. 2 % or more, more preferably 4m 2 % or more, more preferably 8m 2 % or more, particularly preferably 16m 2 % or more, more preferably 28m 2 % or more, most preferably 50m 2 % or more. Also, by increasing A × radio wave transmittance, the amount of radio wave transmission can be increased. There is no problem if A × radio wave transmittance is large, but it is preferable to set it to 8400m 2If A is too large, it becomes difficult to manufacture the glass plate. A x radio wave transmittance is preferably 3000m 2 % or less, more preferably 800m 2 % or less, and even more preferably 400m 2 % or less, particularly preferably 200m 2 % or less, more preferably 120m 2 % or less, most preferably 80m 2 % or less.
[0024] The glass plate according to the present invention preferably has a radio wave transmittance / t of 0.7% / mm to 84% / mm. Here, t is the thickness (mm) of the glass plate, and the radio wave transmittance is the radio wave transmittance (%) at a frequency of 100 GHz converted to a thickness of 18 mm. If the radio wave transmittance / t is 0.7% / mm or more, it is preferable because a higher approximate transmittance can be obtained than that of conventional glass plates. If the radio wave transmittance / thickness t is less than 0.7% / mm, it becomes more difficult to use the glass plate as a window in a high frequency band. The radio wave transmittance / t is preferably 1% / mm or more, more preferably 2% / mm or more, even more preferably 3% / mm or more, particularly preferably 4% / mm or more, even more preferably 5% / mm or more, and most preferably 5.5% / mm or more. By increasing the radio wave transmittance or reducing the thickness, the radio wave transmittance / t becomes large, and the approximate transmittance can be increased. There is no problem in increasing the radio wave transmittance / t, but it is preferably 84% / mm or less. If t becomes too small, the deflection becomes large, making it difficult to use the glass in a large area, and glass with high radio wave transmittance has a high SiO2 content, making it difficult to manufacture glass sheets. In addition, if the radio wave transmittance is high, a large amount of B2O3 must be added, which makes it easier for alkali elements to volatilize during melting and molding, and not only may this lead to a deterioration in glass quality, but also makes it difficult to physically strengthen the glass because the average linear expansion coefficient becomes small. Furthermore, an increase in B2O3 or SiO2 components is likely to lead to a decrease in Young's modulus, which may reduce the rigidity of the substrate and make it difficult to ensure strength during use. In addition, in order to increase the radio wave transmittance, it is necessary to reduce the content of alkali elements, which results in a deterioration in solubility and a significant deterioration in viscosity, which is undesirable, and may also lead to devitrification and hinder glass manufacturing. Therefore, the radio wave transmittance / t is preferably 65% / mm or less, more preferably 50% / mm or less, even more preferably 40% / mm or less, particularly preferably 30% / mm or less, even more preferably 25% / mm or less, and most preferably 20% / mm or less. Furthermore, in consideration of the use, since the glass plate is often thick when used for construction, the lower limit of the radio wave transmittance / t is also preferably small, more preferably 1.3% / mm or more, even more preferably 1.6% / mm or more, particularly preferably 1.8% / mm or more, even more preferably 2.4% / mm or more, and most preferably 3% / mm or more. The upper limit is also preferably small, more preferably 25% / mm or less, even more preferably 15% / mm or less, particularly preferably 11% / mm or less, even more preferably 9% / mm or less, and most preferably 8% / mm or less.
[0025] In the case of use in automobiles, the thickness of the glass plate is, for example, 2 mm to 6 mm, so that the lower limit of the radio wave transmittance / t is more preferably 5% / mm or more, even more preferably 6% / mm or more, particularly preferably 7% / mm or more, even more preferably 7.5% / mm or more, and most preferably 8% / mm or more. The upper limit is more preferably 25% / mm or less, even more preferably 20% / mm or less, particularly preferably 16% / mm or less, even more preferably 13% / mm or less, and most preferably 12% / mm or less. On the other hand, when a thin glass plate of 1 to 2 mm is used, the lower limit of the radio wave transmittance / t is more preferably 15% / mm or more, even more preferably 17% / mm or more, particularly preferably 20% / mm or more, even more preferably 25% / mm or more, and most preferably 30% / mm or more. The upper limit is more preferably 70% / mm or less, even more preferably 60% / mm or less, particularly preferably 55% / mm or less, even more preferably 50% / mm or less, and most preferably 48% / mm or less.
[0026] The glass plate according to the present invention preferably has a specific gravity of 2.40 to 3.00, a Young's modulus of 60 GPa to 100 GPa, and an average linear expansion coefficient from 50° C. to 350° C. of 50×10 -7 / ℃~120×10 -7 / ° C. If the glass sheet satisfies these physical property requirements, it can be used satisfactorily as a window material for buildings, automobiles, etc.
[0027] In order to ensure weather resistance, it is preferable that a certain amount of SiO2 is contained, and the B2O3 content is preferably small. As a result, the specific gravity is preferably 2.40 or more, more preferably 2.42 or more, even more preferably 2.44 or more, even more preferably 2.46 or more, particularly preferably 2.48 or more, even more preferably 2.50 or more, and most preferably 2.52 or more. A specific gravity of 3.0 or less is preferable because it is less likely to become brittle and achieves weight reduction, and is more preferably 2.90 or less, even more preferably 2.80 or less, even more preferably 2.75 or less, particularly preferably 2.70 or less, even more preferably 2.65 or less, and most preferably 2.62 or less.
[0028] A large Young's modulus makes the glass sheet rigid, making it more suitable for architectural applications, automotive applications, etc. The Young's modulus is more preferably 65 GPa or more, even more preferably 70 GPa or more, even more preferably 72 GPa or more, particularly preferably 74 GPa or more, even more preferably 75 GPa or more, and most preferably 76 GPa or more. Increasing SiO2 to increase the Young's modulus leads to poor solubility, so the Young's modulus is preferably 100 GPa or less, more preferably 95 GPa or less, even more preferably 90 GPa or less, even more preferably 85 GPa or less, particularly preferably 82 GPa or less, even more preferably 80 GPa or less, and most preferably 78 GPa or less.
[0029] The average linear expansion coefficient is better to be small from the viewpoint of thermal stress caused by the temperature distribution of the glass plate when it is used. Therefore, the average linear expansion coefficient from 50°C to 350°C is 120×10 -7 / ℃ or less is preferable, and 110×10 -7 / ℃ or less is more preferable, and 100×10 -7 / ℃ or less is more preferable, and 90×10 -7 / ℃ or less is more preferable, and 80×10 -7 / ℃ or less is particularly preferable, and 70×10 -7 / ℃ or less is more preferable, and 60×10 -7 / °C or less is most preferable. However, if the linear expansion coefficient is made too small, the difference in thermal expansion with metal sashes and the like will become large, which may cause distortion and lead to cracks. Therefore, the average linear expansion coefficient from 50°C to 350°C should be less than 35×10 -7 / ℃ or more is preferable, and 40×10 -7 / ℃ or more is more preferable, and 45×10 -7 / ℃ or more is more preferable, and 50×10 -7 / ℃ or more is more preferable, and 55×10 -7 / °C or more is particularly preferred. In addition, for use in construction, automobiles, and the like, it is preferable that physical strengthening is possible, and for this purpose, it is more preferable that the average linear expansion coefficient is large. The average linear expansion coefficient from 50°C to 350°C is more preferably 60×10 -7 / ℃ or more, more preferably 65×10 -7 / °C or more, and particularly preferably 70×10 -7 / °C or more, more preferably 75×10 -7 / ℃ or higher, most preferably 80×10 -7 / ℃ or higher.
[0030] The glass plate according to the present invention preferably has an amount of Na2O eluted of 0.001 mg to 0.6 mg in a water resistance test, the amount of Na2O eluted (mg) being determined according to JIS3502 (1995). A glass plate having an amount of Na2O eluted in a water resistance test of 0.6 mg or less can be used as a window in daily life without problems. The amount of Na2O eluted in a water resistance test is more preferably 0.55 mg or less, even more preferably 0.5 mg or less, particularly preferably 0.4 mg or less, even more preferably 0.35 mg or less, and most preferably 0.3 mg or less. The less the amount of Na2O eluted in a water resistance test, the better, but in order to reduce this amount of elution, SiO2 must be increased, which may increase the viscosity during melting during glass production and cause poor solubility, so the amount of Na2O eluted in a water resistance test is preferably 0.001 mg or more, more preferably 0.01 mg or more, even more preferably 0.05 mg or more, particularly preferably 0.1 mg or more, even more preferably 0.15 mg or more, and most preferably 0.2 mg or more.
[0031] In the glass sheet according to the present invention, T2 is preferably 1750° C. or less. Also, T4 is preferably 1350° C. or less. L In this specification, T2 is the temperature at which the glass viscosity is 10 2 (dPa s), and T4 is the temperature at which the glass viscosity is 10 4 (dPa s), and T L represents the liquidus temperature of the glass. If T2 or T4 is greater than these predetermined temperatures, it becomes difficult to manufacture large plates by the float method, fusion method, roll-out method, down-draw method, etc. T2 is more preferably 1700°C or less, even more preferably 1650°C or less, even more preferably 1625°C or less, particularly preferably 1600°C or less, even more preferably 1575°C or less, even more preferably 1550°C or less, and most preferably 1500°C or less. T4 is preferably 1350°C or less, more preferably 1300°C or less, even more preferably 1250°C or less, particularly preferably 1200°C or less, even more preferably 1150°C or less, even more preferably 1100°C or less, and most preferably 1050°C or less. The lower limits of T2 and T4 are not particularly limited, but in order to maintain weather resistance and glass specific gravity, T2 is typically 1200°C or more and T4 is 800°C or more. T2 is more preferably 1250° C. or higher, even more preferably 1300° C. or higher, particularly preferably 1350° C. or higher, and even more preferably 1400° C. or higher. T4 is more preferably 900° C. or higher, even more preferably 940° C. or higher, particularly preferably 960° C., even more preferably 980° C. or higher, and most preferably 1000° C. or higher. Furthermore, in order to enable manufacturing using the float method, T4-T L is preferably -150°C or higher. L If the T4-T is less than -150°C, devitrification will not occur during glass molding, and problems such as a decrease in the mechanical properties of the glass and a decrease in transparency will not occur, making it possible to obtain glass of good quality, which is preferable. L is more preferably -140°C or less, more preferably -130°C or less, more preferably -120°C or less, more preferably -110°C or less, more preferably -100°C or less. L is more preferably -90°C or higher, more preferably -80°C or higher, more preferably -70°C or higher, even more preferably -60°C or higher, even more preferably -50°C or higher, even more preferably -40°C or higher, even more preferably -30°C or higher, even more preferably -20°C or higher, even more preferably -10°C or higher, particularly preferably 0°C or higher, even more preferably 10°C or higher, and most preferably 20°C or higher.
[0032] The glass plate according to the present invention is g In this specification, T g represents the glass transition temperature. g If the temperature is within this range, the glass can be bent within the normal manufacturing conditions. g If the temperature is lower than 400°C, no problems will occur in formability, but the alkali content or alkaline earth content will be too high, which will tend to cause problems such as excessive thermal expansion of the glass and reduced weather resistance. Furthermore, there is a risk that the glass will devitrify in the forming temperature range, making it impossible to form. g is more preferably 430° C. or higher, further preferably 450° C. or higher, particularly preferably 470° C. or higher, even more preferably 480° C. or higher, and most preferably 490° C. or higher. g If T is too high, a high temperature is required during the glass bending process, making manufacturing more difficult. g is more preferably 650°C or less, more preferably 600°C or less, more preferably 575°C or less, more preferably 565°C or less, even more preferably 555°C or less, particularly preferably 550°C or less, even more preferably 520°C or less, and most preferably 500°C or less.
[0033] The visible light transmittance Tv_A is a visible light transmittance calculated by measuring the transmittance with a spectrophotometer in accordance with JIS R 3106:1998. The weighting coefficient uses the value of a standard A light source and a 2-degree visual field. In this specification, it is expressed as a value converted to a plate thickness of 3.85 mm. Here, the value converted to a plate thickness of 3.85 mm is obtained by measuring the refractive index of the glass plate whose transmittance was measured, and calculating the reflectance of the glass plate from the refractive index using the Sellmeyer equation, and converting the value of the glass plate (here, visible light transmittance Tv_A) to a value for a plate thickness of 3.85 mm, taking multiple reflections into account. The visible light transmittance Tv_A depends on the application, but in order to ensure visibility, it is preferably 30% or more, more preferably 40% or more, even more preferably 50% or more, particularly preferably 60% or more, even more preferably 65% or more, and most preferably 72% or more. The upper limit of the visible light transmittance Tv_A also varies depending on the application, but if it is too high, a large amount of heat rays will also be transmitted, which may deteriorate the heat shielding properties. In addition, in order to increase the visible light transmittance Tv_A, raw materials with few impurities must be used, which makes it difficult to obtain raw materials, and further, it is necessary to make glass with a large SiO2 component, which deteriorates the solubility and makes it difficult to manufacture large glass plates. Therefore, Tv_A is preferably 92% or less. Tv_A is more preferably 91.5% or less, even more preferably 91% or less, particularly preferably 90.5% or less, even more preferably 90% or less, and most preferably 89% or less. The visible light transmittance Tv_A is adjusted mainly by adjusting the amount of coloring components such as Fe2O3 and TiO2, but some adjustment is also possible by adjusting the glass components. It can also be adjusted by adjusting the glass manufacturing conditions, such as the melting temperature and melting atmosphere. When the glass plate according to the present invention is used as a vehicle glass, the visible light transmittance Tv_A is preferably more than 70% in order to improve visibility, more preferably 71% or more, and particularly preferably 72% or more.
[0034] The solar transmittance Te is as defined in ISO-13837A: 2008. In this specification, it is expressed as a value converted to a plate thickness of 3.85 mm. Although the solar radiation transmittance Te depends on the application, if it is too small, the visible light transmittance is likely to decrease and visibility is difficult to ensure. In addition, even if the melting temperature is adjusted, it is difficult to obtain a low Te, so it is difficult to manufacture. The solar radiation transmittance Te is preferably 35% or more, more preferably 40% or more, preferably 45% or more, more preferably 50% or more, even more preferably 55% or more, particularly preferably 60% or more, even more preferably 65% or more, and most preferably 70% or more. In addition, the upper limit of the solar radiation transmittance Te varies depending on the application, but if it is too high, there is a risk that the heat shielding property will deteriorate because many heat rays will also be transmitted. In addition, in order to increase the solar radiation transmittance Te, raw materials with few impurities must be used, which makes it difficult to obtain raw materials, and further, it is necessary to make glass with a large SiO2 component, which deteriorates the solubility and makes it difficult to manufacture large glass plates. Therefore, the solar transmittance Te is preferably 91% or less, more preferably 90% or less, even more preferably 88% or less, particularly preferably 85% or less, even more preferably 80% or less, and most preferably 75% or less. The solar transmittance Te can be adjusted by adjusting coloring components such as Fe2O3 and TiO2, glass components, and further by adjusting glass manufacturing conditions such as the melting temperature and melting atmosphere. When used as a vehicle glass with heat shielding performance, the solar transmittance Te is preferably 65% or less, more preferably 60% or less, even more preferably 58% or less, even more preferably 55% or less, and particularly preferably 53% or less in order to increase the heat shielding performance. On the other hand, if Te is too small, the visible light transmittance decreases and it becomes difficult to ensure visibility, so it is preferably 35% or more, more preferably 38% or more, even more preferably 40% or more, and particularly preferably 41% or more. The ultraviolet transmittance Tuv is defined in ISO-9050:2003. In this specification, it is expressed as a value converted to a plate thickness of 3.85 mm. If the ultraviolet transmittance Tuv is too high, a large amount of ultraviolet light will also be transmitted, which may have an adverse effect on the human body and may cause deterioration of interior materials such as buildings and vehicles in which the glass plate of the present invention is used. Tuv is preferably 90% or less, more preferably 80% or less, even more preferably 70% or less, particularly preferably 50% or less, and most preferably 30% or less. In order to lower Tuv, the glass plate needs to contain Fe2O3, TiO2, CeO2, etc., and if the content of these is high, there is a risk of causing a decrease in visible light transmittance Tv_A and solarization due to sunlight, so Tuv is preferably 1% or more, more preferably 5% or more, and particularly preferably 10% or more. In addition, the ultraviolet transmittance Tuv is preferably 40% or less, more preferably 35% or less, and even more preferably 30% or less in order to prevent deterioration of interior materials and reduce the cooling load inside the car.
[0035] The glass plate according to the present invention can also be used for sensors using infrared rays such as laser radar. When used as glass for vehicles equipped with infrared irradiation equipment such as laser radar, in order to be suitable for use in laser radar, the transmittance at a wavelength of 905 nm converted to a plate thickness of 3.85 mm is preferably 70% or more, more preferably 75% or more, even more preferably 80% or more, particularly preferably 85% or more, particularly preferably 88% or more, and most preferably 90% or more. The glass plate according to the present invention can also be used for infrared sensor applications such as laser radar. When used as vehicle glass equipped with an infrared irradiation device such as laser radar, in order to be suitable for use with the laser radar, the transmittance at a wavelength of 1550 nm converted to a plate thickness of 3.85 mm is preferably 70% or more, more preferably 75% or more, even more preferably 80% or more, particularly preferably 85% or more, particularly preferably 88% or more, and most preferably 90% or more.
[0036] The glass plate according to the present invention can reduce dielectric loss and achieve high radio wave transmittance by adjusting the glass composition. Similarly, the relative dielectric constant can be adjusted by adjusting the composition, and a relative dielectric constant suited to the application can be achieved.
[0037] The glass plate according to the present invention preferably has a SiO2 content of 55% to 75% in terms of mole percentage based on oxides. The Al2O3 content is preferably 0% to 15%. SiO2 and Al2O3 contribute to improving the Young's modulus, making it easier to ensure the strength required for architectural applications, automotive applications, and the like. If the Al2O3 and / or SiO2 content is less than the above lower limit, it is difficult to ensure weather resistance, and the average linear expansion coefficient becomes too large, making it prone to thermal cracking, which is not preferable. If the Al2O3 and / or SiO2 content is too high, it is not preferable because the viscosity during glass melting increases, making glass production difficult. If the Al2O3 content is too high, the radio wave transmittance may also be reduced.
[0038] The SiO2 content is more preferably 57% or more, even more preferably 60% or more, even more preferably 63% or more, particularly preferably 64% or more, even more preferably 65% or more, and most preferably 66% or more. The SiO2 content is more preferably 74% or less, even more preferably 73% or less, particularly preferably 72% or less, even more preferably 70% or less, and most preferably 69% or less. The content of Al2O3 is more preferably 0.3% or more, even more preferably 0.5% or more, even more preferably 1.0% or more, particularly preferably 1.3% or more, even more preferably 1.5% or more, and most preferably 2% or more. In order to keep the glass viscosity T2 low and make the glass easy to manufacture, the content of Al2O3 is more preferably 10% or less, even more preferably 6% or less, even more preferably 5% or less, even more preferably 4% or less, and most preferably 3.5% or less.
[0039] In order to improve the radio wave transmittance, SiO2+Al2O3, i.e., the total of SiO2 content and Al2O3 content, is preferably 50% to 80%. In order to further consider keeping T2 and T4 low and facilitating the production of glass, SiO2+Al2O3 is preferably 80% or less, more preferably 75% or less, even more preferably 72% or less, even more preferably 71% or less, and most preferably 70% or less. However, if SiO2+Al2O3 is too small, there is a risk that the weather resistance will decrease and the average linear expansion coefficient will become too large, so SiO2+Al2O3 is preferably 55% or more, more preferably 64% or more, more preferably 65% or more, even more preferably 66% or more, even more preferably 67% or more, and most preferably 68% or more.
[0040] The glass plate according to the present invention preferably has a B2O3 content of 0% to 15%. The inclusion of B2O3 improves the solubility and glass strength, and has the effect of increasing radio wave transmittance. If the B2O3 content is too high, the alkali elements are likely to volatilize during melting and forming, which may lead to deterioration of glass quality. Furthermore, if the B2O3 content is high, the average linear expansion coefficient decreases, making physical strengthening difficult. The B2O3 content is more preferably 12% or less, even more preferably 10% or less, even more preferably 8% or less, particularly preferably 6% or less, even more preferably 4% or less, and most preferably 2% or less. Furthermore, it is extremely preferable that the glass plate does not substantially contain B2O3.
[0041] The glass plate according to the present invention preferably has an MgO content of 0% to 20%. MgO is a component that promotes the melting of glass raw materials and improves weather resistance. The MgO content is more preferably 0.1% or more, even more preferably 0.2% or more, particularly preferably 0.3% or more, and even more preferably 0.5% or more. If the MgO content is 20% or less, devitrification is less likely to occur and there is a possibility that it is effective in increasing radio wave transmittance. The MgO content is more preferably 15% or less, even more preferably 8% or less, particularly preferably 4% or less, even more preferably 2% or less, and most preferably 1% or less.
[0042] In the glass plate according to the present invention, CaO, SrO, and / or BaO may be contained in a certain amount in order to reduce the dielectric loss of the glass. The content of CaO is preferably 0% or more and 20% or less. The content of SrO is preferably 0% or more and 15% or less. The content of BaO is preferably 0% to 15%. When CaO, SrO, and / or BaO is contained, the meltability of the glass may be improved. The content of CaO is more preferably 3% or more, which reduces the dielectric loss of the glass and improves the radio wave transmittance. In addition, the content of CaO of 3% or more may improve the meltability of the glass (reduction in T2 and reduction in T4). The content of CaO is more preferably 6% or more, particularly preferably 8% or more, even more preferably 10% or more, and most preferably 11% or more. By making CaO 20% or less, SrO 15% or less, and BaO 15% or less, an increase in the specific gravity of the glass is avoided, and low brittleness and strength are maintained. In order to prevent the glass from becoming brittle, the CaO content is more preferably 15% or less, even more preferably 14% or less, particularly preferably 13.5% or less, even more preferably 13% or less, and most preferably 12.5% or less. The SrO content is more preferably 8% or less, even more preferably 3% or less, particularly preferably 2% or less, even more preferably 1% or less, and most preferably substantially free of SrO. The BaO content is more preferably 5% or less, even more preferably 3% or less, particularly preferably 2% or less, even more preferably 1% or less, and most preferably substantially free of BaO.
[0043] In this specification, "RO" represents the total content of MgO, CaO, SrO, and BaO. The glass plate according to the present invention preferably has an RO of 0% to 20%. When the RO is 20% or less, improved weather resistance can be obtained. The RO in the glass plate according to the present invention is more preferably 17% or less, further preferably 16% or less, particularly preferably 15% or less, even more preferably 14% or less, and most preferably 13% or less. From the viewpoint of decreasing T2 and T4 during production or increasing the Young's modulus, the glass plate of the present invention preferably has an RO of more than 0%, more preferably 0.5% or more, further preferably 5% or more, particularly preferably 8% or more, still more preferably 10% or more, and most preferably 12% or more.
[0044] Furthermore, in order to prevent devitrification during glass melting or molding, which leads to deterioration of glass quality, MgO+CaO, i.e., the total content of MgO and CaO, is preferably 0% to 30%. MgO+CaO is more preferably 25% or less, even more preferably 20% or less, even more preferably 15% or less, and most preferably 13% or less. However, if MgO+CaO is too low, the glass viscosity during melting and molding may become too high, making production difficult. Therefore, MgO+CaO is more preferably 1% or more, even more preferably 2% or more, particularly preferably 3% or more, even more preferably 4% or more, and most preferably 5% or more.
[0045] The glass plate according to the present invention preferably has a Na2O content of 0% to 20%. Na2O and K2O are components that improve the melting property of glass, and it is preferable to contain either one or both of them at 0.1% or more, since this makes it easier to keep T2 at 1750°C or less and T4 at 1350°C or less. Furthermore, the inclusion of Na2O enables chemical strengthening. The Na2O content is more preferably 0.1% or more, even more preferably 1% or more, particularly preferably 3% or more, even more preferably 5% or more, and most preferably 6% or more. By including both Na2O and K2O, it is possible to improve weather resistance while maintaining solubility, which is more preferable, and it may also be effective in increasing radio wave transmittance. If the content of Na2O and / or K2O is low, it is possible that the average linear expansion coefficient cannot be increased and thermal strengthening cannot be performed. By setting the content to the above specified amount, it can be used as a window material that is compatible with other components. If the Na2O content is too high, the average linear expansion coefficient becomes too large and the glass becomes susceptible to thermal cracking. The Na2O content is more preferably 16% or less, even more preferably 14% or less, particularly preferably 12% or less, even more preferably 10% or less, and most preferably 8% or less.
[0046] The glass plate according to the present invention preferably has a K2O content of 0% or more to 20%. K2O is a component that improves the melting property of glass, and since it becomes easier to keep T2 at 1750°C or less and T4 at 1350°C or less, the K2O content is more preferably 0.1% or more, even more preferably 0.9% or more, particularly preferably 2% or more, even more preferably 3% or more, and most preferably 4% or more. Also, if the amount of K2O is too large, the average linear expansion coefficient becomes too large, and the material is prone to thermal cracking. If the content of K2O exceeds 20%, the weather resistance decreases, which is not preferable. The content of K2O is more preferably 16% or less, even more preferably 14% or less, particularly preferably 12% or less, even more preferably 10% or less, and most preferably 8% or less. From the viewpoint of radio wave transmittance, a high radio wave transmittance can be obtained by setting the thickness within the above range.
[0047] The glass plate according to the present invention preferably has a Li2O content of 0% to 20%. Li2O is a component that improves the solubility of glass, and also makes it easier to increase the Young's modulus, thereby contributing to improving the strength of glass. By including Li2O, chemical strengthening becomes possible, and it may also be effective in increasing the radio wave transmittance. The Li2O content is more preferably 0.1% or more, further preferably 1% or more, particularly preferably 2% or more, further preferably 3% or more, and most preferably 4% or more. If the amount of Li2O is too large, devitrification or phase separation may occur during glass production, making production difficult. The content of Li2O is more preferably 16% or less, further preferably 12% or less, particularly preferably 8% or less, further preferably 7% or less, and most preferably 6.5% or less.
[0048] In this specification, "R2O" represents the total amount of alkali metal oxides, and usually means the sum of the contents of Li2O, Na2O and K2O. The glass plate according to the present invention preferably has an R2O content of 0% to 20%. If the R2O content is 20% or less, improved weather resistance can be obtained. The R2O content in the glass plate according to the present invention is more preferably 19% or less, further preferably 18.5% or less, particularly preferably 18% or less, even more preferably 17.5% or less, and most preferably 17% or less. Moreover, from the viewpoint of lowering T2 and T4 during production, R2O is preferably more than 0%, more preferably 1% or more, even more preferably 5% or more, still more preferably 6% or more, particularly preferably 8% or more, particularly particularly preferably 10% or more, even more preferably 11% or more, and most preferably 12% or more.
[0049] In order to increase the radio wave transmittance, Na2O / R2O is preferably 0.01 to 0.98. If Na2O / R2O is too small or too large, the effect of increasing the radio wave transmittance may not be sufficiently obtained. Na2O / R2O is preferably 0.01 or more, more preferably 0.05 or more, even more preferably 0.1 or more, particularly preferably 0.2 or more, even more preferably 0.25 or more, and most preferably 0.3 or more. When Li2O is not contained, the lower limit of Na2O / R2O is preferably slightly larger than when Li2O is contained, and Na2O / R2O is preferably 0.01 or more, more preferably 0.1 or more, even more preferably 0.2 or more, particularly preferably 0.3 or more, even more preferably 0.35 or more, and most preferably 0.4 or more. Na2O / R2O is preferably 0.98 or less, more preferably 0.8 or less, even more preferably 0.6 or less, particularly preferably 0.5 or less, even more preferably 0.45 or less, and most preferably 0.4 or less. When Li2O is not contained, the upper limit of Na2O / R2O is preferably slightly larger than when Li2O is contained, and Na2O / R2O is preferably 0.98 or less, more preferably 0.9 or less, even more preferably 0.8 or less, particularly preferably 0.7 or less, even more preferably 0.65 or less, and most preferably 0.6 or less.
[0050] In order to increase the radio wave transmittance, K2O / R2O is preferably 0.01 to 0.98. If K2O / R2O is too small or too large, the effect of increasing the radio wave transmittance may not be sufficiently obtained. K2O / R2O is preferably 0.01 or more, more preferably 0.05 or more, even more preferably 0.1 or more, particularly preferably 0.2 or more, even more preferably 0.25 or more, and most preferably 0.3 or more. When Li2O is not contained, the lower limit of K2O / R2O is preferably slightly larger than when Li2O is contained, and K2O / R2O is preferably 0.01 or more, more preferably 0.1 or more, even more preferably 0.2 or more, particularly preferably 0.3 or more, even more preferably 0.35 or more, and most preferably 0.4 or more. K2O / R2O is preferably 0.98 or less, more preferably 0.8 or less, even more preferably 0.6 or less, particularly preferably 0.5 or less, even more preferably 0.45 or less, and most preferably 0.4 or less. When Li2O is not contained, the upper limit of K2O / R2O is preferably slightly larger than when Li2O is contained, and K2O / R2O is preferably 0.98 or less, more preferably 0.9 or less, even more preferably 0.8 or less, particularly preferably 0.7 or less, even more preferably 0.65 or less, and most preferably 0.6 or less.
[0051] It is preferable to keep the R2O×MgO content low in order to increase the radio wave transmittance. R2O×MgO is preferably 100%. 2 Less than or equal to 80% 2 Less than 66%, more preferably 2 Less than or equal to 60% 2 Less than 50%, especially preferred 2 Less than 40%, more preferably 2 Below 30%, most preferably 2 When Li2O is not contained, the upper limit of R2O×MgO is preferably larger than that when Li2O is contained, and R2O×MgO is preferably 250%. 2 Less than or equal to 200%, preferably 2 Less than or equal to 150%, more preferably2 The following is particularly preferably 100% 2 Less than 85%, more preferably 2 Below 80%, most preferably 2 The following is the result.
[0052] Furthermore, in order to prevent boron and alkali elements from volatilizing during melting and forming, which leads to deterioration of glass quality, R2O+B2O3, i.e., the total content of R2O and B2O3, is preferably 30% or less. R2O+B2O3 is more preferably 25% or less, even more preferably 20% or less, even more preferably 19% or less, and most preferably 18% or less. However, if R2O+B2O3 is too low, the glass viscosity during melting and forming may become too high, making production difficult. Therefore, R2O+B2O3 is preferably 1% or more, more preferably 2% or more, even more preferably 3% or more, even more preferably 4% or more, and most preferably 5% or more.
[0053] In the glass plate according to the present invention, 7Al2O3+3MgO is preferably 0% to 66%. When Al2O3, MgO, and 7Al2O3+3MgO satisfy the above content ranges, the radio wave transmittance of the glass material can be improved. From the viewpoint of radio wave transmittance, it is preferable that 7Al2O3+3MgO is small. Furthermore, if 7Al2O3+3MgO is more than a predetermined amount, it becomes difficult to maintain the average linear expansion coefficient, which may cause a problem in matching with other members or may make physical strengthening difficult. 7Al2O3+3MgO is more preferably 60% or less, even more preferably 55% or less, even more preferably 48% or less, particularly preferably 42% or less, even more preferably 30% or less, and most preferably 24% or less. However, from the viewpoint of weather resistance, the more 7Al2O3+3MgO, the better, 0.5% or more is more preferable, 5% or more is even more preferable, 10% or more is particularly preferable, 15% or more is even more preferable, and 20% or more is the most preferable. This provides sufficient weather resistance.
[0054] In the glass plate according to the present invention, 7Al2O3+3MgO-4Li2O is preferably -60% to 66%. When Al2O3, MgO, Li2O and 7Al2O3+3MgO-4Li2O satisfy the above content ranges, the radio wave transmittance of the glass material can be improved. From the viewpoint of increasing the radio wave transmittance and the Young's modulus, it is preferable that 7Al2O3+3MgO-4Li2O is small. Furthermore, if the amount of 7Al2O3+3MgO-4Li2O is more than a predetermined amount, it becomes difficult to maintain the average linear expansion coefficient, which may cause a problem in matching with other members or may make physical strengthening difficult. 7Al2O3+3MgO-4Li2O is more preferably 50% or less, even more preferably 40% or less, particularly preferably 30% or less, even more preferably 20% or less, and most preferably 10% or less. However, from the viewpoint of weather resistance, the more 7Al2O3+3MgO-4Li2O the better, -50% or more is more preferable, -40% or more is even more preferable, -30% or more is particularly preferable, -20% or more is even more preferable, and -10% or more is most preferable. This provides sufficient weather resistance.
[0055] The glass plate according to the present invention preferably has a ZrO2 content of 0% to 5%. ZrO2 has the effect of lowering the viscosity of glass during melting and promoting melting, and can also contribute to improving heat resistance and chemical durability. If the ZrO2 content is high, the liquidus temperature may rise and the average linear expansion coefficient may increase. The ZrO2 content is more preferably 2.5% or less, even more preferably 2% or less, particularly preferably 1.0% or less, even more preferably 0.5% or less, and most preferably, ZrO2 is substantially not contained.
[0056] The glass plate according to the present invention preferably satisfies 85%≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100%. This makes it possible to manufacture the glass plate from glass raw materials that are easily available, and also makes it easier to ensure the weather resistance of the glass plate. The above total amount is more preferably 88% or more, even more preferably 90% or more, particularly preferably 92% or more, even more preferably 95% or more, even more preferably 98% or more, and most preferably 99.5% or more. Since a colorant, a clarifier, etc. are typically added to a glass plate for a window material, the upper limit of the above total amount is more preferably 99.9%.
[0057] The glass plate according to the present invention preferably has a Fe2O3 content of 0.001% to 5%. Here, the Fe2O3 content refers to the total amount of iron, including FeO, which is an oxide of divalent iron, and Fe2O3, which is an oxide of trivalent iron. If the Fe2O3 content is less than 0.001%, it may not be possible to use the glass plate in applications requiring heat insulation, and it may become necessary to use expensive raw materials with a low iron content to manufacture the glass plate. Furthermore, when melting glass, heat radiation may reach the bottom surface of the melting furnace more than necessary, which may cause a load on the melting furnace, which is not preferable. The Fe2O3 content is more preferably 0.005% or more, even more preferably 0.01% or more, particularly preferably 0.015% or more, even more preferably 0.02% or more, and most preferably 0.05% or more. If Fe2O3 exceeds 5%, heat transfer by radiation may be hindered, and the raw material may not melt easily. Furthermore, if the content of Fe2O3 is too high, the light transmittance in the visible range may decrease (Tv may decrease), and the material may not be suitable for use in automobiles. The content of Fe2O3 is more preferably 2% or less, even more preferably 1% or less, even more preferably 0.8% or less, even more preferably 0.6% or less, particularly preferably 0.5% or less, even more preferably 0.4% or less, and most preferably 0.3% or less.
[0058] In the glass plate according to the present invention, when an infrared irradiation device such as a laser radar is used, the content of divalent iron (FeO) converted to Fe2O3 is preferably 0.0001% to 0.02%. In order to increase the heat ray absorption efficiency of the glass melt during melting of the glass raw material and improve the meltability, the content is preferably 0.0002% or more, more preferably 0.0006% or more, even more preferably 0.0008% or more, and particularly preferably 0.001% or more. In addition, in order to absorb light from the visible range to the near infrared range and to increase the transmittance in the near infrared range, the content is preferably 0.015% or less, more preferably 0.01% or less, even more preferably 0.008% or less, particularly preferably 0.006% or less, and particularly preferably 0.004% or less. In the glass plate according to the present invention, when heat shielding performance is required, the content of divalent iron (FeO) converted to Fe2O3 is preferably 0.05% to 0.16%. Since FeO absorbs light from the visible region to the near infrared region and improves heat shielding performance, the content of FeO is preferably 0.07% or more, more preferably 0.08% or more, even more preferably 0.09% or more, and particularly preferably 0.1% or more. Furthermore, if the content of FeO is high, the glass absorbs heat during production and becomes difficult to manufacture, so the content of FeO is preferably 0.015% or less, more preferably 0.01% or less, even more preferably 0.008% or less, particularly preferably 0.006% or less, and particularly preferably 0.004% or less.
[0059] In the case where an infrared irradiation device such as a laser radar is used, the glass plate according to the present invention preferably has a mass ratio of divalent iron converted to Fe2O3 in the total iron converted to Fe2O3 (hereinafter also referred to as Fe-redox) of more than 0% and 35% or less. Here, the mass ratio of divalent iron converted to Fe2O3 means the ratio of the content after the conversion of FeO, which is an oxide of divalent iron, to the total iron amount. That is, since the molecular weight of FeO is 71.85 g / mol and the molecular weight of Fe2O3 is 159.7 g / mol, the content of divalent iron converted to Fe2O3 is calculated by multiplying the content of FeO by {(159.7÷2) / 71.85}. By making Fe-redox more than 0%, the heat ray absorption efficiency of the glass melt during the melting of the glass raw material can be increased, and the melting property can be improved. Methods for adjusting Fe-redox include, for example, melting at a low temperature and using an oxidizing agent such as cerium oxide or chromium oxide. Fe-redox is preferably 1% or more, more preferably 2% or more, further preferably 3% or more, particularly preferably 4% or more, and most preferably 5% or more.
[0060] In addition, if Fe-redox becomes high, there is a risk of the transmittance in the near infrared region decreasing, so Fe-redox is preferably 35% or less, more preferably 30% or less, even more preferably 25% or less, still more preferably 20% or less, particularly preferably 15% or less, and most preferably 10% or less.
[0061] In the glass plate according to the present invention, when heat insulating performance is required, Fe-redox is preferably more than 30%, more preferably 35% or more, even more preferably 40% or more, even more preferably 45% or more, particularly preferably 50% or more, and most preferably 55% or more. By making Fe-redox more than 30%, the heat insulating property of the glass can be improved. Methods for increasing Fe-redox include, for example, melting at high temperature and using a reducing agent such as tin oxide or coke.
[0062] When the glass plate according to the present invention contains SO3, if it is dissolved under a reducing atmosphere in order to increase Fe-redox, sulfur (S) becomes negative divalent sulfur. As a result, it may react with positive divalent iron in the glass to cause amber coloring and reduce the transmittance in the visible range. Therefore, Fe-redox is preferably 80% or less, more preferably 75% or less, even more preferably 70% or less, even more preferably 65% or less, particularly preferably 60% or less, and most preferably 58% or less.
[0063] The glass plate according to the present invention preferably has a TiO2 content of 0.001% to 5%. If the TiO2 content is less than 0.001%, a bubble layer may be formed on the surface of the molten glass during the production of the glass plate according to the present invention. When the bubble layer is formed, the temperature of the molten glass does not increase, making it difficult to clarify, and productivity tends to deteriorate. In order to thin or eliminate the bubble layer formed on the surface of the molten glass, a titanium compound can be supplied to the bubble layer formed on the surface of the molten glass as a defoaming agent. The titanium compound is taken up in the molten glass and exists as TiO2. This titanium compound may be an inorganic titanium compound (titanium tetrachloride, titanium oxide, etc.) or an organic titanium compound. Examples of the organic titanium compound include titanate esters or derivatives thereof, titanium chelates or derivatives thereof, titanium acylates or derivatives thereof, and oxalic acid titanates. The content of TiO2 is more preferably 0.005% or more, even more preferably 0.01% or more, particularly preferably 0.02% or more, even more preferably 0.05% or more, and most preferably 0.06% or more. In addition, since TiO2 has absorption in the ultraviolet region, it is preferable to add it for applications where ultraviolet rays are to be cut. In that case, the content of TiO2 is preferably 0.04% or more, more preferably 0.1% or more, even more preferably 0.2% or more, and especially preferably 0.5% or more. However, if the content of TiO2 is high, the liquidus temperature may rise and devitrification may occur, and since it has absorption in the visible region and may cause yellow coloring, it is preferable to keep the content of TiO2 at 5% or less. The content of TiO2 is more preferably 1% or less, even more preferably 0.5% or less, especially preferably 0.3% or less, even more preferably 0.2% or less, and most preferably 0.1% or less.
[0064] When an infrared irradiation device such as a laser radar is used, if moisture is present in the glass, the glass plate according to the present invention has absorption in the near infrared region, and the transmittance in the near infrared region is reduced, making it unsuitable for use in the infrared irradiation device. The moisture in the glass can generally be expressed as a value of β-OH, and β-OH is preferably 0.5 or less, more preferably 0.4 or less, even more preferably 0.3 or less, and particularly preferably 0.2 or less. β-OH can be obtained from the transmittance of the glass plate measured using an FT-IR (Fourier transform infrared spectrophotometer) by the following formula. β-OH(mm -1 )=(1 / X)log 10 (T A / T B ) X: Thickness of glass plate (mm) T A :Reference wave number 4000cm -1 Transmittance (%) T B : Hydroxyl group absorption wave number 3600cm -1 Minimum transmittance (%) near
[0065] The glass plate according to the present invention has absorption in the near infrared region when moisture is present in the glass, and therefore can improve the heat shielding property. In order to improve the heat shielding property, the β-OH in the glass is preferably 0.05 or more, more preferably 0.07 or more, further preferably 0.1 or more, and particularly preferably 0.15 or more.
[0066] In the glass plate of the present invention, more excellent properties can be obtained by further setting the composition within the ranges described in the following ten aspects.
[0067] The glass plate according to aspect 1 of the present invention preferably satisfies the following conditions. The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 0≦Al2O3≦9 0≦B2O3≦15 0≦MgO≦15 0≦CaO≦20 0≦SrO≦15 0≦BaO≦15 0≦Li2O<0.01 1.2≦Na2O≦15.6 3.5≦K2O≦12.5 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 4.7≦R2O≦19.5 0≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 42<7Al2O3+3MgO≦66 0.25≦Na2O / R2O≦0.8 R2O+B2O3≦23 0≦PbO<0.001 Including. By setting the range of the first embodiment, it is possible to obtain a glass sheet that exhibits high radio wave transmittance and satisfies the properties required for the desired application.
[0068] In order to increase the radio wave transmittance, the following ranges are more preferred in embodiment 1. The SiO2 content is more preferably 57% or more, and even more preferably 60% or more, in order to increase the Young's modulus and weather resistance. In order to suppress the deterioration of the viscosity due to the increase in viscosity, the SiO2 content is more preferably 70% or less, even more preferably 68% or less, and particularly preferably 66% or less. In order to increase the Young's modulus and weather resistance, the content of Al2O3 is more preferably 2% or more, more preferably 3% or more, even more preferably 4% or more, and particularly preferably 5% or more. In order to increase the radio wave transmittance, the content is more preferably 8% or less, even more preferably 7% or less, even more preferably 6% or less, particularly preferably 5% or less, and most preferably 4.5% or less. From the viewpoint of improving solubility and weather resistance, the content of MgO is more preferably 0.1% or more, even more preferably 0.25% or more, and particularly preferably 0.4% or more. From the viewpoint of improving viscosity, the content is more preferably 13% or less, even more preferably 10% or less, even more preferably 7% or less, particularly preferably 5% or less, particularly preferably 4.5% or less, especially particularly preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and most preferably 1% or less.
[0069] The CaO content is preferably 1% or more in order to improve solubility and increase radio wave transmittance. It is more preferably 2% or more, even more preferably 4% or more, particularly preferably 5% or more, even more preferably 6% or more, and most preferably 8% or more. From the viewpoint of suppressing devitrification, the CaO content is more preferably 18% or less, even more preferably 16% or less, particularly preferably 15% or less, even more preferably 14% or less, particularly preferably 13% or less, and most preferably 12% or less. SrO may be contained to improve solubility and increase radio wave transmittance, and when SrO is contained, its content is preferably 0.5% or more, more preferably 1% or more. In order to prevent the glass from becoming brittle, the SrO content is more preferably 12% or less, even more preferably 10% or less, particularly preferably 8% or less, even more preferably 5% or less, even more preferably 3% or less, and most preferably 2% or less.
[0070] BaO may be contained to improve solubility and increase radio wave transmittance, and when BaO is contained, its content is preferably 0.5% or more, more preferably 1% or more, and particularly preferably 2% or more. In order to prevent the glass from becoming brittle, the BaO content is more preferably 12% or less, even more preferably 10% or less, particularly preferably 9% or less, even more preferably 7% or less, even more preferably 5% or less, and most preferably 3% or less. In order to increase the solubility and adjust the average linear expansion coefficient, the content of Na2O is more preferably 3% or more, even more preferably 4% or more, particularly preferably 5% or more, even more preferably 6% or more, and most preferably 7% or more. In addition, since the inclusion of Na2O deteriorates weather resistance, the content is more preferably 15% or less, even more preferably 14% or less, particularly preferably 13% or less, even more preferably 12% or less, even more preferably 11% or less, and most preferably 10% or less. In order to increase the radio wave transmittance and adjust the average linear expansion coefficient, the content of K2O is more preferably 4% or more, even more preferably 4.5% or more, particularly preferably 5% or more, even more preferably 5.5% or more, and most preferably 6% or more. Furthermore, since the inclusion of K2O deteriorates weather resistance, the content is more preferably 12% or less, even more preferably 11.5% or less, particularly preferably 11% or less, even more preferably 10.5% or less, and most preferably 10% or less.
[0071] ZrO2 may be contained to improve chemical durability, and when ZrO2 is contained, its content is more preferably 0.5% or more. Since there is a risk of the average linear expansion coefficient becoming large, its content is more preferably 1.8% or less, and further preferably 1.5% or less. From the viewpoint of improving solubility, the content of R2O is more preferably 5% or more, more preferably 6% or more, even more preferably 7% or more, still more preferably 8% or more, and particularly preferably 10% or more. On the other hand, in order to improve weather resistance, the content is more preferably 18.5% or less, even more preferably 17% or less, even more preferably 16% or less, particularly preferably 15% or less, and most preferably 14% or less.
[0072] From the viewpoints of improving solubility and radio wave transmittance, the RO content is more preferably 5% or more, even more preferably 7% or more, and particularly preferably 10% or more. On the other hand, from the viewpoints of improving weather resistance and suppressing devitrification, the RO content is more preferably 19% or less, even more preferably 18% or less, even more preferably 17% or less, particularly preferably 16% or less, and most preferably 15% or less. The glass plate according to the present embodiment more preferably satisfies 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100. This makes it possible to produce the glass plate using glass raw materials that are easily available.
[0073] In order to increase radio wave transmittance, 7Al2O3+3MgO is more preferably 43% or more, even more preferably 44% or more, particularly preferably 44.5% or more, even more preferably 45% or more, and most preferably 45.5% or more. Also, 7Al2O3+3MgO is more preferably 60% or less, even more preferably 58% or less, particularly preferably 56% or less, even more preferably 52% or less, and most preferably 50% or less. In order to increase the radio wave transmittance, Na2O / R2O is more preferably 0.3 or more, even more preferably 0.35 or more, particularly preferably 0.4 or more, even more preferably 0.43 or more, and most preferably 0.45 or more. Na2O / R2O is more preferably 0.75 or less, even more preferably 0.7 or less, particularly preferably 0.65 or less, even more preferably 0.6 or less, and most preferably 0.55 or less.
[0074] In the first aspect of the present invention, SiO2+Al2O3 is preferably 50% or more, more preferably 55% or more, particularly preferably 60% or more, even more preferably 65% or more, even more preferably 67% or more, and most preferably 68% or more. Also, SiO2+Al2O3 is preferably 80% or less, more preferably 78% or less, particularly preferably 76% or less, even more preferably 74% or less, and most preferably 72% or less. It is preferable to lower R2O×MgO in order to increase radio wave transmittance. When Li2O is not contained, the upper limit of R2O×MgO is preferably as large as possible, and is preferably 250%. 2 The following is the result. In order to prevent boron and alkali elements from volatilizing during melting and forming, which leads to deterioration of glass quality, R2O+B2O3 is preferably 23% or less. R2O+B2O3 is more preferably 22% or less, more preferably 21% or less, even more preferably 20% or less, even more preferably 19% or less, and most preferably 18.5% or less. However, if R2O+B2O3 is too low, the glass viscosity during melting and forming may become too high, making production difficult. Therefore, R2O+B2O3 is preferably 1% or more, more preferably 4% or more, even more preferably 8% or more, even more preferably 10% or more, and most preferably 12% or more. In order to prevent boron and alkali elements from volatilizing during melting and forming, which would lead to a deterioration in glass quality, the B2O3 content is preferably 15% or less, more preferably 12% or less, more preferably 10% or less, more preferably 7% or less, even more preferably 5% or less, still more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and most preferably 1% or less. In order to prevent devitrification during glass melting and forming, which leads to deterioration of glass quality, MgO+CaO is more preferably 20% or less, even more preferably 18% or less, particularly preferably 16% or less, even more preferably 15% or less, even more preferably 14% or less, and most preferably 13% or less. However, if MgO+CaO is too low, the glass viscosity during melting and forming may become too high, making production difficult, so MgO+CaO is preferably 1% or more, more preferably 2% or more, even more preferably 4% or more, even more preferably 5% or more, even more preferably 7% or more, most preferably 9% or more, and most preferably 10% or more. If the glass plate satisfies these conditions, it is possible to obtain high radio wave transmittance in the high frequency band.
[0075] The glass plate according to aspect 2 of the present invention preferably satisfies the following conditions. The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 0≦Al2O3≦6 0≦B2O3≦15 0≦MgO≦14 0≦CaO≦20 0≦SrO≦15 0≦BaO≦15 0≦Li2O<0.01 4≦Na2O≦17 1.9≦K2O≦14.2 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦3 5.9≦R2O≦20 0≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 23.5<7Al2O3+3MgO≦42 0.22≦Na2O / R2O≦0.85 R2O×MgO≦66 55≦SiO2+Al2O3≦76 0≦PbO<0.001 Including. By setting the range of the second embodiment, it is possible to obtain a glass sheet that exhibits high radio wave transmittance and satisfies the properties required for the desired application.
[0076] In order to increase the radio wave transmittance, it is more preferable to set the range as follows in the second embodiment. In order to increase the Young's modulus and weather resistance, the SiO2 content is more preferably 60% or more, even more preferably 65% or more, even more preferably 66% or more, particularly preferably 67% or more, and most preferably 68% or more, and from the viewpoint of improving viscosity, the SiO2 content is more preferably 74% or less, even more preferably 73% or less, particularly preferably 72% or less, and most preferably 71% or less. In order to increase the Young's modulus and weather resistance, the Al2O3 content is more preferably 0.5% or more, even more preferably 1% or more, particularly preferably 1.5% or more, and most preferably 2% or more, and in order to increase the radio wave transmittance, the Al2O3 content is more preferably 5% or less, even more preferably 4% or less, and even more preferably 3% or less. From the viewpoint of improving solubility and weather resistance, the MgO content is more preferably 0.1% or more, even more preferably 0.25% or more, and particularly preferably 0.35% or more, and from the viewpoint of improving viscosity, the MgO content is more preferably 13% or less, even more preferably 10% or less, even more preferably 9% or less, even more preferably 7% or less, particularly preferably 5% or less, especially particularly preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and most preferably 1% or less.
[0077] In order to improve solubility and increase radio wave transmittance, the CaO content is preferably 1% or more, more preferably 3% or more, even more preferably 4% or more, particularly preferably 6% or more, even more preferably 8% or more, and most preferably 10% or more. From the viewpoint of suppressing devitrification, the CaO content is more preferably 18% or less, even more preferably 17% or less, particularly preferably 16% or less, even more preferably 15% or less, and most preferably 14% or less. SrO may be contained to improve solubility and to increase radio wave transmittance, and when SrO is contained, its content is preferably 0.5% or more, more preferably 1% or more. In order to prevent the glass from becoming brittle, the SrO content is more preferably 12% or less, even more preferably 10% or less, particularly preferably 7% or less, even more preferably 4% or less, and most preferably 2% or less.
[0078] BaO may be contained to improve solubility and increase radio wave transmittance, and when BaO is contained, the content is preferably 0.5% or more, more preferably 1% or more, and particularly preferably 2% or more. In order to prevent the glass from becoming brittle, the BaO content is more preferably 12% or less, even more preferably 10% or less, particularly preferably 8% or less, even more preferably 5% or less, and most preferably 3% or less. In order to ensure solubility while also increasing radio wave transmittance, the Na2O content is preferably 4% to 17%. By setting it in this range, it becomes easier to properly maintain the range of Na2O / R2O and the range of R2O×MgO described below, and weather resistance is also ensured. The Na2O content is more preferably 4.5% or more, even more preferably 5% or more, and most preferably 6% or more. In addition, the Na2O content is more preferably 16% or less, even more preferably 14% or less, particularly preferably 12% or less, even more preferably 11% or less, and most preferably 10% or less.
[0079] In order to increase radio wave transmittance, the content of K2O is more preferably 2% or more, even more preferably 3.5% or more, even more preferably 4% or more, particularly preferably 5% or more, even more preferably 5.5% or more, and most preferably 6% or more, and is more preferably 13.5% or less, even more preferably 12% or less, particularly preferably 11% or less, even more preferably 10.5% or less, and most preferably 10% or less. ZrO2 may be contained to improve chemical durability, and when ZrO2 is contained, its content is more preferably 0.5% or more. Since there is a risk of the average linear expansion coefficient becoming large, the content of ZrO2 is more preferably 1.8% or less, and further preferably 1.5% or less.
[0080] From the viewpoint of improving solubility, the content of R2O is more preferably 7% or more, further preferably 8% or more, and particularly preferably 10% or more. On the other hand, in order to improve weather resistance, the content is more preferably 18% or less, further preferably 16% or less, even more preferably 14% or less, particularly preferably 13% or less, and most preferably 12% or less. From the viewpoints of improving solubility and radio wave transmittance, the RO content is more preferably 2% or more, more preferably 5% or more, even more preferably 7% or more, even more preferably 8% or more, and particularly preferably 10% or more. On the other hand, from the viewpoints of improving weather resistance and suppressing devitrification, the RO content is more preferably 19% or less, even more preferably 18% or less, even more preferably 17% or less, particularly preferably 16% or less, and most preferably 15% or less.
[0081] The glass plate according to aspect 2 more preferably satisfies 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100. This makes it possible to produce the glass plate from easily available glass raw materials. In order to increase radio wave transmittance, 7Al2O3+3MgO is more preferably 24% or more, even more preferably 25% or more, particularly preferably 26% or more, even more preferably 28% or more, and most preferably 30% or more. Also, 7Al2O3+3MgO is more preferably 40% or less, even more preferably 38% or less, particularly preferably 37% or less, even more preferably 36% or less, and most preferably 35% or less. In order to increase the radio wave transmittance, Na2O / R2O is more preferably 0.3 or more, even more preferably 0.35 or more, particularly preferably 0.4 or more, and most preferably 0.45 or more. Na2O / R2O is more preferably 0.8 or less, even more preferably 0.75 or less, particularly preferably 0.7 or less, even more preferably 0.6 or less, and most preferably 0.55 or less.
[0082] In order to improve the solubility and the radio wave transmittance, SiO2+Al2O3 is more preferably 60% or more, even more preferably 65% or more, particularly preferably 67% or more, and most preferably 68% or more. In addition, SiO2+Al2O3 is preferably 76% or less, more preferably 75% or less, even more preferably 74% or less, particularly preferably 73% or less, and most preferably 72% or less. It is preferable to make R2O×MgO low in order to increase the radio wave transmittance. R2O×MgO is preferably 66%. 2 Less than or equal to 60%, more preferably 2 Less than 50%, more preferably 2 Less than 40%, particularly preferably 2 Less than 30%, more preferably 2 Below 25%, most preferably 2 The following is the result. In order to prevent boron and alkali elements from volatilizing during melting and forming, leading to deterioration of glass quality, R2O+B2O3 is preferably 30% or less, more preferably 28% or less, even more preferably 25% or less, even more preferably 20% or less, even more preferably 18% or less, and most preferably 16% or less. However, if R2O+B2O3 is too low, the glass viscosity during melting and forming may become too high, making production difficult, so R2O+B2O3 is preferably 1% or more, more preferably 2% or more, even more preferably 3% or more, even more preferably 4% or more, even more preferably 6% or more, and most preferably 8% or more.
[0083] In order to prevent a high Na2O content from causing boron and alkali elements to volatilize during melting and forming, which would lead to a deterioration in glass quality, the B2O3 content is preferably 15% or less. The B2O3 content is more preferably 12% or less, even more preferably 10% or less, still more preferably 8% or less, even more preferably 6% or less, and most preferably 5% or less. In order to prevent devitrification during glass melting and forming, which leads to deterioration of glass quality, MgO+CaO is more preferably 18% or less, even more preferably 16% or less, even more preferably 14% or less, and most preferably 12% or less. However, if MgO+CaO is too low, the glass viscosity during melting and forming may become too high, making production difficult, so MgO+CaO is preferably 1% or more, more preferably 2% or more, even more preferably 3% or more, even more preferably 4% or more, and most preferably 5% or more. Since the glass plate according to embodiment 2 is prone to devitrification, the TiO2 content is preferably 3% or less, more preferably 2% or less, even more preferably 1% or less, particularly preferably 0.5% or less, even more preferably 0.2% or less, and most preferably 0.1% or less.
[0084] The glass plate according to aspect 3 of the present invention preferably satisfies the following conditions. The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 1.3≦Al2O3≦3.35 0≦B2O3≦15 0≦MgO≦4.8 0≦CaO≦20 0≦SrO≦4 0≦BaO≦15 0≦Li2O<0.01 0.1≦Na2O≦16 1≦K2O≦16 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦1.5 1.1≦R2O≦20 0≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 0≦7Al2O3+3MgO≦23.5 0.05≦Na2O / R2O≦0.8 0≦R2O+B2O3≦22 0≦PbO<0.001 0≦ZnO≦8 Including. By setting the range of the third embodiment, it is possible to obtain a glass sheet that exhibits high radio wave transmittance and satisfies the properties required for the desired application.
[0085] In order to increase the radio wave transmittance, it is more preferable to set the range as follows in the third embodiment. In order to increase the Young's modulus and weather resistance, the SiO2 content is more preferably 60% or more, even more preferably 65% or more, and particularly preferably 68% or more. From the viewpoint of improving viscosity, the SiO2 content is more preferably 74% or less, even more preferably 73.5% or less, particularly preferably 73% or less, and most preferably 72.5% or less. In order to increase the Young's modulus and weather resistance, Al2O3 is more preferably 1.5% or more, further preferably 1.7% or more, particularly preferably 1.9% or more, and most preferably 2% or more. In order to increase the radio wave transmittance, Al2O3 is more preferably 3.0% or less, and further preferably 2.5% or less.
[0086] From the viewpoint of improving solubility and weather resistance, the content of MgO is more preferably 0.1% or more, further preferably 0.25% or more, and particularly preferably 0.5% or more. From the viewpoint of improving viscosity, the content of MgO is more preferably 4% or less, further preferably 3% or less, particularly preferably 2% or less, and most preferably 1% or less. In order to improve solubility and increase radio wave transmittance, the CaO content is preferably 1% or more, more preferably 2% or more, even more preferably 4% or more, particularly preferably 5% or more, even more preferably 6% or more, and most preferably 8% or more. In order to suppress devitrification, the CaO content is more preferably 18% or less, even more preferably 16% or less, particularly preferably 15% or less, even more preferably 14% or less, and most preferably 13% or less.
[0087] BaO may be contained to improve solubility and increase radio wave transmittance, and when BaO is contained, its content is preferably 0.5% or more, more preferably 1% or more, and particularly preferably 2% or more. In order to prevent the glass from becoming brittle, the BaO content is more preferably 12% or less, even more preferably 10% or less, even more preferably 9% or less, particularly preferably 8% or less, most particularly preferably 4% or less, and most preferably 3% or less. In order to increase the solubility and adjust the average linear expansion coefficient, the content of Na2O is more preferably 2% or more, even more preferably 4% or more, particularly preferably 5% or more, even more preferably 6% or more, and most preferably 7% or more. Furthermore, since the inclusion of Na2O deteriorates weather resistance, the content is more preferably 15% or less, even more preferably 14% or less, particularly preferably 13% or less, even more preferably 12% or less, and most preferably 11% or less. In order to increase radio wave transmittance, the content of K2O is more preferably 1.5% or more, even more preferably 2% or more, particularly preferably 2.5% or more, and most preferably 3% or more, and is more preferably 13% or less, even more preferably 11% or less, particularly preferably 10% or less, even more preferably 9% or less, and most preferably 8% or less.
[0088] ZrO2 may be contained to improve chemical durability, and when ZrO2 is contained, the content is more preferably 0.5% or more. The content of ZrO2 is more preferably 1.8% or less, and further preferably 1.5% or less, since there is a risk of the average linear expansion coefficient becoming large. From the viewpoint of improving solubility, R2O is more preferably 5% or more, even more preferably 6% or more, particularly preferably 8% or more, and most preferably 10% or more. On the other hand, in order to improve weather resistance, it is more preferably 19% or less, even more preferably 17% or less, even more preferably 15% or less, particularly preferably 14.5% or less, and most preferably 14% or less. From the viewpoints of improving solubility and radio wave transmittance, RO is more preferably 5% or more, even more preferably 6% or more, and particularly preferably 9% or more. On the other hand, from the viewpoints of improving weather resistance and suppressing devitrification, RO is more preferably 18% or less, even more preferably 16% or less, even more preferably 15% or less, particularly preferably 13% or less, and most preferably 12% or less.
[0089] In order to increase radio wave transmittance, 7Al2O3+3MgO is more preferably 0.5% or more, even more preferably 1% or more, particularly preferably 5% or more, even more preferably 8% or more, and most preferably 10% or more. Also, 7Al2O3+3MgO is more preferably 23% or less, even more preferably 22.5% or less, and even more preferably 22% or less. In order to increase the radio wave transmittance, Na2O / R2O is more preferably 0.1 or more, even more preferably 0.15 or more, particularly preferably 0.2 or more, even more preferably 0.25 or more, and most preferably 0.3 or more. Na2O / R2O is more preferably 0.75 or less, even more preferably 0.7 or less, particularly preferably 0.65 or less, especially particularly preferably 0.6 or less, and most preferably 0.55 or less. SiO2+Al2O3 is more preferably 50% or more, even more preferably 55% or more, particularly preferably 60% or more, even more preferably 65% or more, even more preferably 68% or more, and most preferably 71% or more. SiO2+Al2O3 is more preferably 80% or less, even more preferably 78% or less, particularly preferably 76% or less, even more preferably 75% or less, and most preferably 74% or less.
[0090] It is preferable to lower the R2O×MgO ratio in order to increase the radio wave transmittance. The R2O×MgO ratio is preferably 80%. 2 Less than or equal to 60%, more preferably 2 Less than 40%, more preferably 2 Less than 30%, particularly preferably 2 Less than 20%, more preferably 2 Less than or equal to 10%, most preferably 2 The following is the result. In order to prevent boron and alkali elements from volatilizing during melting and forming, which would lead to a deterioration in glass quality, R2O+B2O3 is preferably 22% or less, more preferably 20% or less, even more preferably 18.5% or less, even more preferably 18% or less, and most preferably 16% or less. However, if R2O+B2O3 is too low, the glass viscosity during melting and forming may become too high, making production difficult. Therefore, R2O+B2O3 is preferably 1% or more, more preferably 2% or more, even more preferably 4% or more, even more preferably 6% or more, and most preferably 8% or more. Also in embodiment 3, since the Na2O component in the glass increases relatively to the total alkali amount, the boron and alkali elements volatilize during melting and forming, which would lead to a deterioration in glass quality, the B2O3 content is preferably 15% or less, more preferably 10% or less, even more preferably 8% or less, even more preferably 6% or less, and most preferably 5% or less. The glass plate according to the third embodiment is more preferably 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100. This makes it possible to manufacture the glass plate from glass raw materials that are easily available. In addition, in a composition with low Al2O3 and MgO content, such as the glass of this embodiment, the total amount is more preferably 98% or more in order to ensure the weather resistance of the glass plate. The above total amount is more preferably 98.5% or more, and particularly preferably 99% or more. Since a colorant, a clarifier, etc. are typically added to a glass plate for a window material, the upper limit of the above total amount is even more preferably 99.9%. In addition, in embodiment 3, in order to prevent the glass from becoming brittle and losing strength due to small amounts of Al2O3 and MgO, or to reduce the weight of the glass sheet, the content of SrO is preferably 4% or less, more preferably 2.5% or less, even more preferably 2% or less, and particularly preferably substantially none.
[0091] In order to prevent devitrification during glass melting and forming, which leads to deterioration of glass quality, MgO+CaO is preferably 18% or less, more preferably 16% or less, even more preferably 14% or less, even more preferably 13% or less, and most preferably 12% or less. However, if MgO+CaO is too low, the glass viscosity during melting and forming may become too high, making production difficult, so MgO+CaO is preferably 1% or more, more preferably 2% or more, even more preferably 3% or more, even more preferably 4% or more, and most preferably 5% or more. Since the glass plate according to embodiment 3 is particularly prone to devitrification, the TiO content is preferably 1.5% or less, more preferably 1% or less, even more preferably 0.5% or less, particularly preferably 0.2% or less, even more preferably 0.1% or less, and most preferably 0.05% or less. The glass sheet according to embodiment 3 may contain ZnO since it has an effect of suppressing devitrification. If a large amount of ZnO is contained, defects may occur during production in a float bath, and therefore the ZnO content is preferably 8% or less, more preferably 6% or less, more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, even more preferably 1% or less, and even more preferably 0.5% or less.
[0092] The glass plate according to aspect 4 of the present invention preferably satisfies the following conditions. The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 1.44≦Al2O3≦9 0≦B2O3≦2 0≦MgO≦15 0≦CaO≦20 0≦SrO≦15 0≦BaO≦1 0.01≦Li2O≦19.1 0≦Na2O≦16 0.9≦K2O≦16 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 0.91≦R2O≦20 0≦RO≦20 98≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 10<7Al2O3+3MgO-4Li2O≦66 0≦Na2O / R2O≦0.8 0≦PbO<0.001 Including. By setting the range of the fourth embodiment, it is possible to obtain a glass sheet that exhibits high radio wave transmittance and satisfies the properties required for the desired application.
[0093] In order to increase the radio wave transmittance, it is more preferable to set the range as follows in embodiment 4. In order to increase the Young's modulus and weather resistance, the SiO2 content is more preferably 60% or more, even more preferably 64% or more, and particularly preferably 65% or more, and from the viewpoint of improving viscosity, the SiO2 content is more preferably 72% or less, even more preferably 70% or less, and particularly preferably 68% or less. In order to enhance the solubility and adjust the average linear expansion coefficient, the NaO content is more preferably 2% or more, more preferably 3% or more, even more preferably 4% or more, particularly preferably 5% or more, and even more preferably 6% or more, and in order to enhance the weather resistance, the NaO content is more preferably 15% or less, even more preferably 14% or less, particularly preferably 13% or less, even more preferably 12% or less, still more preferably 10% or less, and most preferably 9% or less.
[0094] In order to increase radio wave transmittance, the content of K2O is more preferably 1% or more, even more preferably 1.5% or more, particularly preferably 2% or more, even more preferably 2.5% or more, and most preferably 3% or more, and is more preferably 15% or less, even more preferably 13% or less, particularly preferably 12% or less, even more preferably 10% or less, and most preferably 9% or less. In order to increase the solubility and Young's modulus and improve the radio wave transmittance, the LiO content is more preferably 1% or more, even more preferably 2% or more, particularly preferably 3% or more, and even more preferably 4% or more. Since LiO has the risk of devitrification and phase separation, the LiO content is more preferably 15% or less, even more preferably 12% or less, particularly preferably 10% or less, even more preferably 8% or less, and most preferably 7% or less. SrO may be contained to improve solubility and to increase radio wave transmittance, and when SrO is contained, its content is preferably 0.5% or more, more preferably 1% or more, and particularly preferably 2% or more. In order to prevent the glass from becoming brittle, the SrO content is more preferably 12% or less, even more preferably 10% or less, particularly preferably 8% or less, even more preferably 6% or less, and most preferably 4% or less.
[0095] In order to increase radio wave transmittance, 7Al2O3+3MgO-4Li2O is more preferably 12 or more, even more preferably 14 or more, particularly preferably 16 or more, even more preferably 18 or more, and most preferably 20 or more. In addition, 7Al2O3+3MgO-4Li2O is more preferably 60 or less, even more preferably 55 or less, particularly preferably 50 or less, even more preferably 45 or less, and most preferably 40 or less. In order to increase the radio wave transmittance, Na2O / R2O is more preferably 0.05 or more, even more preferably 0.1 or more, particularly preferably 0.15 or more, even more preferably 0.2 or more, and most preferably 0.25 or more. Na2O / R2O is more preferably 0.8 or less, even more preferably 0.75 or less, particularly preferably 0.7 or less, even more preferably 0.6 or less, and most preferably 0.5 or less.
[0096] In the fourth embodiment, in order to reduce the glass viscosity during melting and molding to facilitate production, SiO2+Al2O3 is preferably 50% or more, more preferably 60% or more, particularly preferably 65% or more, even more preferably 66% or more, and most preferably 68% or more. Also, SiO2+Al2O3 is preferably 75% or less, more preferably 74% or less, particularly preferably 73% or less, even more preferably 72% or less, and most preferably 71% or less. In order to reduce the glass viscosity during melting and molding to facilitate production and to increase radio wave transmittance, the Al2O3 content is preferably 9% or less, more preferably 8% or less, even more preferably 7% or less, particularly preferably 6% or less, even more preferably 5% or less, and most preferably 4% or less, and in order to ensure weather resistance, the Al2O3 content is more preferably 1.5% or more, even more preferably 2% or more, and particularly preferably 2.5% or more. In order to increase the radio wave transmittance, K2O / R2O is more preferably 0.05 or more, even more preferably 0.1 or more, particularly preferably 0.15 or more, even more preferably 0.2 or more, and most preferably 0.25 or more. In addition, K2O / R2O is more preferably 0.95 or less, even more preferably 0.9 or less, particularly preferably 0.7 or less, even more preferably 0.5 or less, and most preferably 0.4 or less.
[0097] In the fourth embodiment, in order to increase the radio wave transmittance, it is more preferable to lower R2O×MgO. R2O×MgO is preferably 200%. 2 Less than or equal to 180%, more preferably 2 Less than or equal to 160%, more preferably 2 Below 140%, particularly preferably 2 Less than or equal to 120, more preferably less than or equal to 100% 2 Below 80%, most preferably 2 The following is the result. In order to prevent boron and alkali elements from volatilizing during melting and forming, which would lead to a deterioration in glass quality, R2O+B2O3 is preferably 19% or less, more preferably 18.5% or less, even more preferably 18% or less, even more preferably 17% or less, and most preferably 16% or less. However, if R2O+B2O3 is too low, the glass viscosity during melting and forming may become too high, making production difficult, so R2O+B2O3 is preferably 1% or more, more preferably 2% or more, even more preferably 3% or more, even more preferably 4% or more, and most preferably 5% or more. In order to prevent boron and alkali elements from volatilizing during melting and forming, which would lead to a deterioration in glass quality, the B2O3 content is preferably 2% or less, more preferably 1.8% or less, even more preferably 1.5% or less, even more preferably 1.0% or less, and most preferably 0.5% or less.
[0098] In order to prevent devitrification during glass melting and forming, which leads to deterioration of glass quality, MgO+CaO is preferably 20% or less, more preferably 18% or less, even more preferably 16% or less, even more preferably 15% or less, and most preferably 14% or less. However, if MgO+CaO is too low, the glass viscosity during melting and forming may become too high, making production difficult, so MgO+CaO is preferably 1% or more, more preferably 2% or more, even more preferably 4% or more, even more preferably 6% or more, and most preferably 8% or more. Furthermore, in order to prevent the glass from becoming brittle and losing strength, or to reduce the weight of the glass sheet, the BaO content is preferably 1% or less, more preferably 0.5% or less, even more preferably 0.1% or less, and particularly preferably substantially none is contained. Similarly to the above, in order to prevent the glass from becoming brittle and losing strength, or to reduce the weight of the glass plate, SrO+BaO+ZrO2 is preferably 8% or less, more preferably 7% or less, even more preferably 6% or less, particularly preferably 5% or less, even more preferably 3% or less, and most preferably 2% or less. Furthermore, in order to increase radio wave transmittance, MgO is more preferably 14% or less, even more preferably 12% or less, particularly preferably 10% or less, even more preferably 8% or less, even more preferably 6% or less, and most preferably 4.5% or less. In order to improve the solubility and increase the radio wave transmittance, the CaO content is preferably 0.5% or more, more preferably 1% or more, even more preferably 3% or more, particularly preferably 5% or more, even more preferably 7% or more, and most preferably 8% or more, and from the viewpoint of suppressing devitrification, the CaO content is more preferably 18% or less, even more preferably 16% or less, particularly preferably 14% or less, even more preferably 13% or less, and most preferably 12% or less.
[0099] ZrO2 may be contained to improve chemical durability, and when ZrO2 is contained, its content is more preferably 0.5% or more. Also, since there is a risk of the average linear expansion coefficient becoming large, its content is more preferably 1.8% or less, and further preferably 1.5% or less. From the viewpoint of improving solubility, R2O is more preferably 5% or more, more preferably 6% or more, even more preferably 7% or more, and particularly preferably 8% or more. On the other hand, in order to improve weather resistance, it is more preferably 18% or less, even more preferably 17% or less, even more preferably 16% or less, particularly preferably 15% or less, and most preferably 14% or less. From the viewpoints of improving solubility and improving radio wave transmittance, RO is more preferably 5% or more, even more preferably 6% or more, and particularly preferably 8% or more. On the other hand, from the viewpoints of improving weather resistance and suppressing devitrification, RO is more preferably 19% or less, even more preferably 18% or less, even more preferably 17% or less, particularly preferably 16% or less, and most preferably 15% or less.
[0100] The glass plate according to aspect 5 of the present invention preferably satisfies the following conditions. The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 0≦Al2O3≦7.8 0≦B2O3≦2 0≦MgO≦11.8 2≦CaO≦20 0≦SrO≦15 0≦BaO≦1 2.5≦Li2O≦19.52 0.15≦Na2O≦17.17 0.33≦K2O≦16.5 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 2.98≦R2O≦20 2≦RO≦20 98≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 -10<7Al2O3+3MgO-4Li2O≦10 0.05≦Na2O / R2O≦0.85 0.11≦K2O / R2O≦0.83 0≦PbO<0.001 Including. By setting the range of the fifth embodiment, it is possible to obtain a glass sheet that exhibits high radio wave transmittance and satisfies the properties required for the desired application.
[0101] In order to increase the radio wave transmittance, it is more preferable to set the range as follows in the fifth embodiment. In order to increase the Young's modulus and weather resistance, the SiO2 content is more preferably 60% or more, even more preferably 63% or more, and particularly preferably 65% or more, and from the viewpoint of improving viscosity, the SiO2 content is more preferably 73% or less, more preferably 71% or less, even more preferably 70% or less, and particularly preferably 69% or less. The NaO content is more preferably 0.5% or more, more preferably 1% or more, more preferably 2% or more, more preferably 3% or more, even more preferably 4% or more, and particularly preferably 5% or more in order to increase the solubility and adjust the average linear expansion coefficient, and is more preferably 15% or less, even more preferably 13% or less, particularly preferably 11% or less, even more preferably 10% or less, and most preferably 8% or less in order to improve the weather resistance. In order to increase radio wave transmittance, the content of K2O is more preferably 0.5% or more, more preferably 2% or more, even more preferably 3% or more, particularly preferably 4% or more, even more preferably 5% or more, and most preferably 6% or more, and from the viewpoint of improving viscosity, the content is more preferably 16% or less, even more preferably 14% or less, particularly preferably 12% or less, even more preferably 11% or less, and most preferably 10% or less.
[0102] The content of Li2O is more preferably 3% or more, even more preferably 4% or more, and particularly preferably 5% or more in order to increase the solubility and Young's modulus and improve the radio wave transmittance. In addition, since there is a concern that Li2O may cause devitrification and phase separation, the content is more preferably 15% or less, even more preferably 12% or less, particularly preferably 10% or less, even more preferably 8% or less, and most preferably 7% or less. In order to increase the radio wave transmittance, 7Al2O3+3MgO-4Li2O is more preferably -9 or more, even more preferably -6 or more, particularly preferably -4 or more, even more preferably -2 or more, and most preferably -1 or more. Also, 7Al2O3+3MgO-4Li2O is more preferably 9.5 or less, even more preferably 9 or less, particularly preferably 8.5 or less, and even more preferably 8 or less.
[0103] SrO may be contained to improve solubility and to increase radio wave transmittance, and when SrO is contained, its content is preferably 0.5% or more, more preferably 1% or more, and particularly preferably 2% or more. In order to prevent the glass from becoming brittle, the SrO content is more preferably 12% or less, even more preferably 10% or less, particularly preferably 8% or less, even more preferably 6% or less, and most preferably 4% or less. In order to increase the radio wave transmittance, Na2O / R2O is more preferably 0.1 or more, even more preferably 0.15 or more, particularly preferably 0.2 or more, even more preferably 0.25 or more, and most preferably 0.3 or more. Na2O / R2O is more preferably 0.9 or less, even more preferably 0.8 or less, particularly preferably 0.7 or less, even more preferably 0.6 or less, and most preferably 0.5 or less.
[0104] In embodiment 5, SiO2+Al2O3 is more preferably 50% or more, even more preferably 55% or more, particularly preferably 60% or more, even more preferably 65% or more, even more preferably 67% or more, and most preferably 68% or more. Also, SiO2+Al2O3 is more preferably 80% or less, even more preferably 78% or less, particularly preferably 76% or less, even more preferably 75% or less, even more preferably 74% or less, even more preferably 73% or less, and most preferably 72.5% or less. In order to reduce the glass viscosity during melting and molding to facilitate production and to increase radio wave transmittance, the content of Al2O3 is more preferably 7% or less, even more preferably 6% or less, particularly preferably 5% or less, even more preferably 4.5% or less, even more preferably 3% or less, and most preferably 3.5% or less. There is no particular lower limit for Al2O3, but in order to ensure weather resistance, the content of Al2O3 is more preferably 0.5% or more, even more preferably 1% or more, particularly preferably 1.5% or more, especially particularly preferably 1.8% or more, even more preferably 2% or more, and most preferably 2.5% or more. In order to increase the radio wave transmittance, K2O / R2O is more preferably 0.15 or more, even more preferably 0.2 or more, particularly preferably 0.25 or more, even more preferably 0.28 or more, and most preferably 0.3 or more. Moreover, K2O / R2O is more preferably 0.80 or less, even more preferably 0.7 or less, particularly preferably 0.6 or less, even more preferably 0.5 or less, and most preferably 0.4 or less. By setting Na2O / R2O and K2O / R2O within a predetermined range, it is preferable because it is easy to increase the radio wave transmittance.
[0105] In the fifth aspect, it is more preferable to lower R2O×MgO in order to increase the radio wave transmittance. R2O×MgO is preferably 200%. 2 Less than or equal to 150% 2 Less than or equal to 130%, more preferably 2 Less than or equal to 120% 2 or less, more preferably 100% or less 2 , and even more preferably 80% 2 Less than 60%, especially preferred 2 Less than 40%, more preferably 2 Below 30%, most preferably 2 The following is the result. In order to prevent boron and alkali elements from volatilizing during melting and forming, which leads to deterioration of glass quality, R2O+B2O3 is preferably 19% or less. R2O+B2O3 is more preferably 18.5% or less, even more preferably 18% or less, even more preferably 17% or less, and most preferably 16% or less. However, if R2O+B2O3 is too low, the glass viscosity during melting and forming may become too high, making production difficult. Therefore, R2O+B2O3 is preferably 1% or more, more preferably 2% or more, even more preferably 4% or more, even more preferably 6% or more, and most preferably 8% or more. In order to prevent boron and alkali elements from volatilizing during melting and forming, which would lead to deterioration of glass quality, the B2O3 content is preferably 2% or less, more preferably 1.5% or less, even more preferably 1% or less, and most preferably 0.5% or less. In order to prevent devitrification during glass melting and forming, which leads to deterioration of glass quality, MgO+CaO is preferably 17% or less, more preferably 15% or less, even more preferably 14% or less, and even more preferably 13% or less. However, if MgO+CaO is too low, the glass viscosity during melting and forming may become too high, making production difficult, so MgO+CaO is preferably 1% or more, more preferably 2% or more, even more preferably 4% or more, even more preferably 6% or more, and most preferably 8% or more.
[0106] Furthermore, in order to prevent the glass from becoming brittle and losing strength, or to reduce the weight of the glass sheet, BaO is preferably contained in an amount of 1% or less, more preferably 0.8% or less, more preferably 0.5% or less, even more preferably 0.1% or less, and particularly preferably substantially none. As described above, in order to prevent the glass from becoming brittle and losing strength, or to reduce the weight of the glass plate, the content of SrO+BaO+ZrO2 is more preferably 12% or less, even more preferably 10% or less, particularly preferably 8% or less, even more preferably 4% or less, and most preferably 2% or less. Furthermore, in order to increase radio wave transmittance, the content of MgO is preferably 11.8% or less, more preferably 10% or less, even more preferably 7% or less, particularly preferably 6% or less, even more preferably 5% or less, even more preferably 4% or less, even more preferably 3% or less, and most preferably 2% or less. From the viewpoint of improving solubility, the content is preferably 0% or more, more preferably 0.1% or more, even more preferably 0.3% or more, and particularly preferably 0.5% or more. In order to improve the solubility and increase the radio wave transmittance, the CaO content is preferably 2% or more, more preferably 3% or more, even more preferably 4% or more, particularly preferably 5% or more, even more preferably 6% or more, and most preferably 8% or more. From the viewpoint of suppressing devitrification, the CaO content is more preferably 18% or less, even more preferably 17% or less, particularly preferably 16% or less, even more preferably 14% or less, and most preferably 12% or less.
[0107] ZrO2 may be contained to improve chemical durability. If ZrO2 is contained, its content is more preferably 0.5% or more. Since there is a risk of the average linear expansion coefficient becoming large, its content is more preferably 1.8% or less, and even more preferably 1.5% or less. From the viewpoint of improving solubility, RO is more preferably 5% or more, more preferably 6% or more, more preferably 7% or more, even more preferably 9% or more, and particularly preferably 10% or more, while in order to improve weather resistance, RO is more preferably 18% or less, even more preferably 16.5% or less, even more preferably 15.5% or less, particularly preferably 14.5% or less, and most preferably 13.5% or less. From the viewpoints of improving solubility and radio wave transmittance, RO is more preferably 5% or more, even more preferably 7% or more, particularly preferably 8% or more, and most preferably 10% or more. On the other hand, from the viewpoints of improving weather resistance and suppressing devitrification, RO is more preferably 19% or less, even more preferably 18% or less, even more preferably 17% or less, particularly preferably 16% or less, and most preferably 14% or less.
[0108] The glass plate according to embodiment 6 of the present invention preferably satisfies the following conditions. The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 0≦Al2O3≦5.5 0≦B2O3≦2 0≦MgO≦10.5 0≦CaO≦20 0≦SrO≦15 0≦BaO≦15 2.5≦Li2O≦20 0≦Na2O≦18.5 0≦K2O≦18.5 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 2.5≦R2O≦20 0≦RO≦20 98≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 -60≦7Al2O3+3MgO-4Li2O≦-10 0≦PbO<0.001 Including. By setting the range of the sixth embodiment, it is possible to obtain a glass sheet that exhibits high radio wave transmittance and satisfies the properties required for the desired application.
[0109] In order to increase the radio wave transmittance, it is more preferable to set the range as follows in the sixth embodiment. In order to increase the Young's modulus and weather resistance, the SiO2 content is more preferably 60% or more, even more preferably 63% or more, and particularly preferably 65% or more, and from the viewpoint of improving viscosity, the SiO2 content is more preferably 72% or less, even more preferably 71% or less, and particularly preferably 70% or less. The content of Na2O is more preferably 1% or more, further preferably 2% or more, particularly preferably 3% or more in order to increase the solubility and adjust the average linear expansion coefficient. Furthermore, since the inclusion of Na2O deteriorates the weather resistance, the content is more preferably 15% or less, further preferably 12% or less, particularly preferably 10% or less, even more preferably 8% or less, and most preferably 7% or less. In order to increase radio wave transmittance, the content of K2O is more preferably 0.5% or more, more preferably 1% or more, even more preferably 2% or more, even more preferably 3% or more, and particularly preferably 4% or more, and from the viewpoint of improving viscosity, the content is more preferably 15.5% or less, even more preferably 14% or less, particularly preferably 12% or less, even more preferably 10% or less, even more preferably 8% or less, and most preferably 7% or less.
[0110] The content of Li2O is more preferably 3% or more, and even more preferably 4% or more, in order to increase the solubility and Young's modulus and improve the radio wave transmittance. Also, since Li2O may cause devitrification and phase separation, the content is more preferably 15% or less, more preferably 14% or less, more preferably 13% or less, even more preferably 12% or less, particularly preferably 10% or less, even more preferably 8% or less, and most preferably 7% or less. The content of SrO may be included to improve solubility and to increase radio wave transmittance, and when SrO is included, it is preferably 0.5% or more, more preferably 1% or more, and particularly preferably 2% or more. In order to prevent the glass from becoming brittle, the content of SrO is more preferably 12% or less, even more preferably 10% or less, particularly preferably 8% or less, even more preferably 6% or less, and most preferably 4% or less.
[0111] In order to improve the water resistance of the glass, 7Al2O3+3MgO-4Li2O is more preferably -50 or more, even more preferably -40 or more, particularly preferably -35 or more, even more preferably -30 or more, and most preferably -25 or more. In order to increase the radio wave transmittance of the glass, 7Al2O3+3MgO-4Li2O is more preferably -10.5 or less, even more preferably -11 or less, even more preferably -12 or less, particularly preferably -13 or less, even more preferably -14 or less, and most preferably -15 or less. In order to increase radio wave transmittance, Na2O / R2O is more preferably 0.05 or more, even more preferably 0.1 or more, particularly preferably 0.15 or more, even more preferably 0.2 or more, and most preferably 0.25 or more. From the viewpoint of improving weather resistance, Na2O / R2O is more preferably 0.95 or less, even more preferably 0.9 or less, particularly preferably 0.8 or less, even more preferably 0.6 or less, even more preferably 0.5 or less, and most preferably 0.4 or less.
[0112] In the sixth embodiment, in order to reduce the viscosity during glass melting and molding and to facilitate production, SiO2+Al2O3 is preferably 50% or more, more preferably 55% or more, particularly preferably 60% or more, even more preferably 65% or more, and most preferably 68% or more. In addition, SiO2+Al2O3 is preferably 80% or less, more preferably 78% or less, particularly preferably 76% or less, even more preferably 74% or less, and most preferably 72.5% or less. In order to reduce the glass viscosity during melting and molding and facilitate production, the Al2O3 content is more preferably 5% or less, even more preferably 4.5% or less, particularly preferably 4% or less, even more preferably 3.5% or less, and most preferably 3% or less. There is no particular lower limit for Al2O3, but in order to ensure weather resistance, the Al2O3 content is more preferably 0.1% or more, more preferably 0.2% or more, more preferably 0.5% or more, even more preferably 1% or more, particularly preferably 1.5% or more, and even more preferably 2% or more. In order to increase the radio wave transmittance, K2O / R2O is more preferably 0.05 or more, even more preferably 0.1 or more, particularly preferably 0.15 or more, even more preferably 0.2 or more, and most preferably 0.25 or more. In addition, in terms of improving weather resistance, K2O / R2O is more preferably 0.95 or less, even more preferably 0.9 or less, particularly preferably 0.7 or less, even more preferably 0.5 or less, and most preferably 0.4 or less. By setting Na2O / R2O and K2O / R2O within a predetermined range, it is easier to increase the radio wave transmittance, which is preferable.
[0113] In the sixth aspect, it is more preferable to lower R2O×MgO in order to increase the radio wave transmittance. R2O×MgO is more preferably 200%. 2 Less than or equal to 160%, more preferably 2 Less than or equal to 120% 2 Less than or equal to 100%, more preferably 2 Less than or equal to 80% 2 Less than 60%, especially preferred 2 Less than 40%, more preferably 2 Below 20%, most preferably 2 The following is the result. In order to prevent boron and alkali elements from volatilizing during melting and forming, which would lead to a deterioration in glass quality, R2O+B2O3 is preferably 19% or less, more preferably 18.5% or less, even more preferably 18% or less, even more preferably 17% or less, and most preferably 16% or less. However, if R2O+B2O3 is too low, the glass viscosity during melting and forming may become too high, making production difficult, so R2O+B2O3 is preferably 2.5% or more, more preferably 5% or more, even more preferably 10% or more, even more preferably 12% or more, and most preferably 13% or more. In order to prevent boron and alkali elements from volatilizing during melting and forming, which would lead to a deterioration in glass quality, B2O3 is preferably 2% or less, more preferably 1.5% or less, even more preferably 1% or less, still more preferably 0.75% or less, and most preferably 0.5% or less.
[0114] In order to prevent devitrification during glass melting and molding, which leads to deterioration of glass quality, MgO+CaO is preferably 15% or less, more preferably 14% or less, and even more preferably 13% or less. However, if MgO+CaO is too low, the glass viscosity during melting and molding may become too high, making production difficult. Therefore, MgO+CaO is preferably 1% or more, more preferably 2% or more, even more preferably 4% or more, even more preferably 6% or more, and most preferably 8% or more. Furthermore, in order to prevent the glass from becoming brittle and losing strength, or to reduce the weight of the glass sheet, the BaO content is preferably 15% or less, more preferably 8% or less, even more preferably 4% or less, particularly preferably 2% or less, even more preferably 1% or less, still more preferably 0.5% or less, and most preferably substantially none.
[0115] Similarly, in order to prevent the glass from becoming brittle and losing strength, or to reduce the weight of the glass sheet, SrO+BaO+ZrO2 is preferably 15% or less, more preferably 14% or less, even more preferably 10% or less, even more preferably 8% or less, particularly preferably 5% or less, even more preferably 4% or less, and most preferably 2% or less. Furthermore, in order to increase radio wave transmittance, MgO is more preferably 10.5% or less, even more preferably 8% or less, particularly preferably 6% or less, even more preferably 4% or less, and most preferably 2% or less. From the viewpoint of improving solubility, MgO is preferably 0% or more, more preferably 0.1% or more, even more preferably 0.2% or more, particularly preferably 0.3% or more, and most preferably 0.5% or more. In order to improve the solubility and increase the radio wave transmittance, the CaO content is more preferably 0.5% or more, even more preferably 1% or more, particularly preferably 2% or more, even more preferably 3% or more, even more preferably 6% or more, and most preferably 8% or more. From the viewpoint of suppressing devitrification, the CaO content is more preferably 18% or less, even more preferably 17% or less, particularly preferably 16% or less, even more preferably 15% or less, and most preferably 14% or less.
[0116] ZrO2 may be contained to improve chemical durability, and when ZrO2 is contained, its content is more preferably 0.5% or more. Since there is a risk of the average linear expansion coefficient becoming large, its content is more preferably 1.8% or less, and further preferably 1.5% or less. From the viewpoint of improving solubility, R2O is more preferably 5% or more, more preferably 6% or more, more preferably 7% or more, even more preferably 8% or more, particularly preferably 10% or more, and most preferably 12% or more. On the other hand, in order to improve weather resistance, it is more preferably 18% or less, even more preferably 16% or less, even more preferably 15% or less, and particularly preferably 14.5% or less. From the viewpoints of improving solubility and radio wave transmittance, RO is more preferably 5% or more, even more preferably 7% or more, particularly preferably 10% or more, and most preferably 12% or more. On the other hand, from the viewpoints of improving weather resistance and suppressing devitrification, RO is more preferably 19% or less, even more preferably 18% or less, even more preferably 17% or less, particularly preferably 16% or less, and most preferably 15% or less.
[0117] The glass plate according to embodiment 7 of the present invention preferably satisfies the following conditions. The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 1.44≦Al2O3≦9 0.5≦B2O3≦13 0≦MgO≦15 0≦CaO≦20 0≦SrO≦15 0≦BaO≦1 0.01≦Li2O≦19.1 0≦Na2O≦16 0.9≦K2O≦16 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 0.91≦R2O≦20 0≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 10<7Al2O3+3MgO-4Li2O≦66 0≦Na2O / R2O≦0.8 0≦PbO<0.001 0≦ZnO≦3 Including. By setting the range of the seventh embodiment, it is possible to obtain a glass sheet that exhibits high radio wave transmittance and satisfies the properties required for the desired application.
[0118] In order to increase the radio wave transmittance, it is more preferable to set the range as follows in the seventh embodiment. In order to increase the Young's modulus and weather resistance, SiO2 is more preferably 60% or more, more preferably 62% or more, even more preferably 64% or more, and particularly preferably 65% or more. In terms of improving viscosity, SiO2 is more preferably 73% or less, even more preferably 71% or less, even more preferably 70% or less, and particularly preferably 68% or less. In order to increase the solubility and adjust the average linear expansion coefficient, the content of Na2O is more preferably 1% or more, even more preferably 1.5% or more, particularly preferably 2% or more, even more preferably 2.5% or more, even more preferably 3% or more, and most preferably 4% or more. Furthermore, since the inclusion of Na2O deteriorates weather resistance, the content is more preferably 15% or less, even more preferably 14% or less, particularly preferably 13% or less, even more preferably 12% or less, even more preferably 10% or less, and most preferably 8% or less. In order to increase radio wave transmittance, the content of K2O is more preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, particularly preferably 2% or more, even more preferably 3% or more, and most preferably 4% or more. The content of K2O is more preferably 15% or less, even more preferably 13% or less, particularly preferably 12% or less, even more preferably 10% or less, and most preferably 8% or less.
[0119] The content of Li2O is more preferably 1% or more, even more preferably 2% or more, particularly preferably 3% or more, and even more preferably 4% or more in order to increase the solubility and Young's modulus and improve the radio wave transmittance. In addition, since the inclusion of Li2O may cause devitrification and phase separation, the content is more preferably 15% or less, even more preferably 12% or less, particularly preferably 10% or less, even more preferably 8% or less, and most preferably 6% or less. SrO may be contained to improve solubility and increase radio wave transmittance, and when SrO is contained, its content is preferably 0.5% or more, more preferably 1% or more, and particularly preferably 2% or more. In order to prevent the glass from becoming brittle, the SrO content is more preferably 12% or less, even more preferably 10% or less, particularly preferably 8% or less, even more preferably 6% or less, and most preferably 4% or less.
[0120] In order to increase radio wave transmittance, 7Al2O3+3MgO-4Li2O is more preferably 11 or more, even more preferably 13 or more, particularly preferably 15 or more, even more preferably 17 or more, and most preferably 19 or more. In addition, 7Al2O3+3MgO-4Li2O is more preferably 60 or less, even more preferably 50 or less, particularly preferably 45 or less, even more preferably 40 or less, and most preferably 35 or less. In order to increase the radio wave transmittance, Na2O / R2O is more preferably 0.05 or more, even more preferably 0.1 or more, particularly preferably 0.15 or more, even more preferably 0.2 or more, even more preferably 0.25 or more, and most preferably 0.3 or more. Na2O / R2O is more preferably 0.85 or less, even more preferably 0.8 or less, particularly preferably 0.6 or less, even more preferably 0.5 or less, and most preferably 0.4 or less.
[0121] In the seventh embodiment, in order to reduce the glass viscosity during melting and molding to facilitate production, SiO2+Al2O3 is preferably at least 50, more preferably at least 55, particularly preferably at least 60, even more preferably at least 65, and most preferably at least 67. In addition, SiO2+Al2O3 is preferably at most 75, more preferably at most 74, particularly preferably at most 73, even more preferably at most 72, and most preferably at most 71. In order to lower the glass viscosity during melting and molding to facilitate production and to increase radio wave transmittance, the Al2O3 content is preferably 9% or less. The Al2O3 content is more preferably 8% or less, even more preferably 7% or less, particularly preferably 6% or less, and even more preferably 5% or less. In order to ensure weather resistance, the Al2O3 content is more preferably 1.5% or more, even more preferably 2% or more, and particularly preferably 2.5% or more. In order to increase the radio wave transmittance, K2O / R2O is more preferably 0.05 or more, even more preferably 0.1 or more, particularly preferably 0.15 or more, even more preferably 0.2 or more, even more preferably 0.25 or more, and most preferably 0.30 or more. In addition, K2O / R2O is more preferably 0.95 or less, even more preferably 0.8 or less, particularly preferably 0.7 or less, even more preferably 0.6 or less, even more preferably 0.5 or less, and most preferably 0.4 or less.
[0122] In the seventh aspect, it is more preferable to lower R2O×MgO in order to increase the radio wave transmittance. R2O×MgO is preferably 200%. 2 Less than or equal to 180%, more preferably 2 Less than or equal to 160%, more preferably 2 Below 140%, particularly preferably 2 Less than 120%, more preferably 2 More preferably, 100% 2 Below 80%, most preferably 2 The following is the result. In order to prevent boron and alkali elements from volatilizing during melting and forming, which would lead to a deterioration in glass quality, R2O+B2O3 is preferably 25% or less. More preferably, it is 23% or less, even more preferably, it is 20% or less, even more preferably, it is 18% or less, and most preferably, it is 16% or less. However, if R2O+B2O3 is too low, the glass viscosity during melting and forming may become too high, which may make production difficult. Therefore, R2O+B2O3 is preferably 1% or more, more preferably, it is 2% or more, even more preferably, it is 4% or more, even more preferably, it is 6% or more, and most preferably, it is 8% or more. In order to prevent boron and alkali elements from volatilizing during melting and forming, which would lead to a deterioration in glass quality, the content of B2O3 is preferably 13% or less, more preferably 12% or less, even more preferably 10% or less, even more preferably 8% or less, and most preferably 6% or less. In order to improve solubility, the content of B2O3 is preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, and particularly preferably 2% or more.
[0123] In order to prevent devitrification during glass melting and forming, which leads to deterioration of glass quality, MgO+CaO is preferably 15% or less, more preferably 14% or less, even more preferably 13% or less, even more preferably 12% or less, and most preferably 10% or less. However, if MgO+CaO is too low, the glass viscosity during melting and forming may become too high, making production difficult, so MgO+CaO is preferably 1% or more, more preferably 2% or more, even more preferably 4% or more, even more preferably 5% or more, and most preferably 6% or more. Furthermore, in order to prevent the glass from becoming brittle and losing strength, or to reduce the weight of the glass sheet, BaO is preferably 1% or less, more preferably 0.5% or less, even more preferably 0.1% or less, and particularly preferably substantially not contained. Similarly to the above, in order to prevent the glass from becoming brittle and losing strength, or in order to reduce the weight of the glass plate, SrO+BaO+ZrO2 is preferably 10% or less, more preferably 8% or less, even more preferably 6% or less, particularly preferably 5% or less, even more preferably 4% or less, and most preferably 3% or less.
[0124] Furthermore, in order to increase radio wave transmittance, the MgO content is more preferably 10% or less, even more preferably 8% or less, particularly preferably 6% or less, even more preferably 4.5% or less, even more preferably 3% or less, and most preferably 2% or less. In order to improve the solubility and increase the radio wave transmittance, the CaO content is more preferably 0.5% or more. The CaO content is more preferably 1% or more, even more preferably 3% or more, particularly preferably 5% or more, even more preferably 6% or more, and most preferably 7% or more. From the viewpoint of suppressing devitrification, the CaO content is more preferably 18% or less, even more preferably 15% or less, particularly preferably 14% or less, even more preferably 12% or less, and most preferably 10% or less.
[0125] ZrO2 may be contained to improve chemical durability, and when ZrO2 is contained, its content is more preferably 0.5% or more. Since the average linear expansion coefficient may increase with the content of ZrO2, it is more preferably 1.8% or less, and further preferably 1.5% or less. From the viewpoint of improving solubility, the content of RO is more preferably 5% or more, more preferably 6% or more, even more preferably 7% or more, and particularly preferably 8% or more, while in order to improve weather resistance, the content is more preferably 18% or less, even more preferably 17% or less, even more preferably 16% or less, particularly preferably 15% or less, and most preferably 14% or less. From the viewpoints of improving solubility and improving radio wave transmittance, the RO content is more preferably 5% or more, even more preferably 7% or more, and particularly preferably 10% or more. On the other hand, from the viewpoints of improving weather resistance and suppressing devitrification, the RO content is more preferably 19% or less, even more preferably 18% or less, even more preferably 17% or less, particularly preferably 15% or less, and most preferably 13% or less. The glass plate according to this embodiment may contain ZnO since it has an effect of suppressing devitrification. If a large amount of ZnO is contained, defects may occur during production in a float bath, so the ZnO content is preferably 3% or less. The ZnO content is more preferably 2% or less, more preferably 1.5% or less, and even more preferably 1% or less, and it is preferable that ZnO is not substantially contained.
[0126] The glass plate according to embodiment 8 of the present invention preferably satisfies the following conditions. The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 1≦Al2O3≦7.8 0.5≦B2O3≦15 0≦MgO≦11.8 2≦CaO≦20 0≦SrO≦15 0≦BaO≦1 4.25≦Li2O≦19.15 0.25≦Na2O≦15.15 0.60≦K2O≦15.5 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 5.10≦R2O≦20 2≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 -10<7Al2O3+3MgO-4Li2O≦10 0.05≦Na2O / R2O≦0.95 0.11≦K2O / R2O≦0.9 0≦PbO<0.001 Including. By setting the range of embodiment 8, it is possible to obtain a glass sheet that exhibits high radio wave transmittance and satisfies the properties required for the desired application.
[0127] In order to increase the radio wave transmittance, it is more preferable to set the range as follows in embodiment 8. In order to increase the Young's modulus and weather resistance, the SiO2 content is more preferably 60% or more, further preferably 63% or more, and particularly preferably 65% or more. From the viewpoint of improving viscosity, the SiO2 content is more preferably 73% or less, further preferably 72% or less, and particularly preferably 70% or less. The content of Na2O is more preferably 2% or more, even more preferably 4% or more, and particularly preferably 5% or more in order to increase the solubility and adjust the average linear expansion coefficient. Furthermore, since the inclusion of Na2O deteriorates the weather resistance, the content is more preferably 15% or less, even more preferably 13% or less, particularly preferably 11% or less, even more preferably 10% or less, and most preferably 8% or less. In order to increase radio wave transmittance, the content of K2O is more preferably 1.0% or more, even more preferably 2% or more, particularly preferably 4% or more, and even more preferably 5% or more. The content of K2O is more preferably 15% or less, even more preferably 14% or less, particularly preferably 12% or less, even more preferably 10% or less, and most preferably 8% or less.
[0128] The content of Li2O is more preferably 4.5% or more, even more preferably 5.0% or more, particularly preferably 5.5% or more, and even more preferably 6.0% or more in order to increase the solubility and Young's modulus and improve the radio wave transmittance. In addition, since the inclusion of Li2O may cause devitrification and phase separation, the content is more preferably 15% or less, more preferably 12% or less, more preferably 10% or less, even more preferably 9% or less, particularly preferably 8% or less, even more preferably 7% or less, and most preferably 6% or less. In order to increase the radio wave transmittance, 7Al2O3+3MgO-4Li2O is more preferably -9 or more, even more preferably -6 or more, particularly preferably -4 or more, even more preferably -2 or more, and most preferably -1 or more. Also, 7Al2O3+3MgO-4Li2O is more preferably 9 or less, even more preferably 8 or less, particularly preferably 7 or less, even more preferably 6 or less, and most preferably 5 or less. SrO may be contained to improve solubility and to increase radio wave transmittance, and when SrO is contained, its content is preferably 0.5% or more, more preferably 1% or more, and particularly preferably 2% or more. In order to prevent the glass from becoming brittle, the SrO content is more preferably 12% or less, even more preferably 10% or less, particularly preferably 8% or less, even more preferably 6% or less, and most preferably 4% or less. In order to increase the radio wave transmittance, Na2O / R2O is more preferably 0.1 or more, even more preferably 0.15 or more, particularly preferably 0.2 or more, even more preferably 0.25 or more, and most preferably 0.3 or more. Na2O / R2O is more preferably 0.9 or less, even more preferably 0.8 or less, particularly preferably 0.7 or less, even more preferably 0.6 or less, even more preferably 0.5 or less, and most preferably 0.4 or less.
[0129] In embodiment 8, SiO2+Al2O3 is more preferably 50% or more, even more preferably 55% or more, particularly preferably 60% or more, even more preferably 65% or more, and most preferably 68% or more. Also, SiO2+Al2O3 is more preferably 80% or less, even more preferably 78% or less, particularly preferably 75% or less, even more preferably 74% or less, even more preferably 73% or less, and most preferably 72% or less. In order to reduce the glass viscosity during melting and molding to facilitate production and to increase radio wave transmittance, the content of Al2O3 is more preferably 7% or less. Al2O3 is further preferably 6% or less, particularly preferably 5% or less, and most preferably 4% or less. In order to ensure weather resistance, Al2O3 is more preferably 1.5% or more, further preferably 2% or more, and particularly preferably 2.5% or more. In order to increase the radio wave transmittance, K2O / R2O is more preferably 0.15 or more, even more preferably 0.2 or more, particularly preferably 0.25 or more, even more preferably 0.28 or more, and most preferably 0.3 or more. Moreover, K2O / R2O is more preferably 0.85 or less, even more preferably 0.8 or less, particularly preferably 0.7 or less, even more preferably 0.5 or less, and most preferably 0.4 or less. By setting Na2O / R2O and K2O / R2O within a predetermined range, it is preferable because it is easy to increase the radio wave transmittance.
[0130] In the eighth aspect, it is more preferable to lower R2O×MgO in order to increase the radio wave transmittance. R2O×MgO is preferably 200%. 2 Less than or equal to 150% 2Less than or equal to 100%, more preferably 2 Less than 60%, especially preferred 2 Less than 50%, more preferably 2 Less than 40%, more preferably 2 Below 30%, most preferably 2 The following is the result. In order to prevent boron and alkali elements from volatilizing during melting and forming, which leads to deterioration of glass quality, R2O+B2O3 is preferably 25% or less, more preferably 22% or less, even more preferably 20% or less, even more preferably 19% or less, and most preferably 18% or less. However, if R2O+B2O3 is too low, the glass viscosity during melting and forming may become too high, making production difficult. Therefore, R2O+B2O3 is preferably 1% or more, more preferably 2% or more, even more preferably 4% or more, even more preferably 6% or more, and most preferably 10% or more. In order to prevent boron and alkali elements from volatilizing during melting and forming, which would lead to a deterioration in glass quality, the B2O3 content is preferably 12% or less, further preferably 8% or less, even more preferably 6% or less, and most preferably 5% or less. In order to improve solubility, the B2O3 content is preferably 0.5% or more. The B2O3 content is more preferably 1% or more, and further preferably 2% or more. In order to prevent devitrification during glass melting and molding, which leads to deterioration of glass quality, MgO+CaO is preferably 15% or less, more preferably 14% or less, even more preferably 13% or less, even more preferably 12% or less, and most preferably 10% or less. However, if MgO+CaO is too low, the glass viscosity during melting and molding may become too high, making production difficult. Therefore, MgO+CaO is preferably 1% or more, more preferably 2% or more, even more preferably 3% or more, even more preferably 4% or more, and most preferably 5% or more.
[0131] Furthermore, in order to prevent the glass from becoming brittle and losing strength, or in order to reduce the weight of the glass sheet, the BaO content is preferably 1% or less, more preferably 0.5% or less, even more preferably 0.1% or less, and particularly preferably substantially none is contained. As described above, in order to prevent the glass from becoming brittle and losing strength, or to reduce the weight of the glass plate, the content of SrO+BaO+ZrO2 is more preferably 12% or less, even more preferably 8% or less, particularly preferably 5% or less, even more preferably 4% or less, and most preferably 3% or less. Furthermore, in order to increase radio wave transmittance, the MgO content is preferably 11.8% or less, more preferably 10% or less, even more preferably 8% or less, particularly preferably 6% or less, even more preferably 4% or less, and most preferably 2% or less. In order to improve the solubility and to increase the radio wave transmittance, the CaO content is preferably 2% or more, more preferably 3% or more, even more preferably 4% or more, particularly preferably 5% or more, and even more preferably 6% or more. From the viewpoint of suppressing devitrification, the CaO content is more preferably 18% or less, even more preferably 16% or less, particularly preferably 14% or less, even more preferably 12% or less, even more preferably 10% or less, even more preferably 9% or less, and most preferably 8% or less. The content of ZrO2 may be contained to improve chemical durability, and when ZrO2 is contained, the content is more preferably 0.5% or more. Since there is a risk of the average linear expansion coefficient becoming large, the content is more preferably 1.8% or less, and further preferably 1.5% or less. From the viewpoint of improving solubility, the content of R2O is more preferably 6% or more, even more preferably 7% or more, and particularly preferably 8% or more. On the other hand, in order to improve weather resistance, the content is more preferably 18% or less, even more preferably 16% or less, even more preferably 15% or less, even more preferably 14.5% or less, and particularly preferably 13.5% or less. From the viewpoints of improving solubility and radio wave transmittance, the RO content is more preferably 4% or more, even more preferably 6% or more, and particularly preferably 7% or more. On the other hand, from the viewpoints of improving weather resistance and suppressing devitrification, the RO content is more preferably 19% or less, even more preferably 18% or less, even more preferably 17% or less, even more preferably 16% or less, particularly preferably 14% or less, and most preferably 12% or less.
[0132] The glass plate according to embodiment 9 of the present invention preferably satisfies the following conditions. The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 0.5≦Al2O3≦15 0≦B2O3≦15 0≦MgO≦15 0≦CaO≦20 0≦SrO≦15 0≦BaO≦15 3.4 <Li2O≦20 0≦Na2O≦16.6 0≦K2O≦16.6 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 3.4 <R2O≦20 1≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 -60≦7Al2O3+3MgO-4Li2O≦-10 0≦PbO<0.001 Including. By setting the range of the ninth embodiment, it is possible to obtain a glass sheet that exhibits high radio wave transmittance and satisfies the properties required for the desired application.
[0133] In order to increase the radio wave transmittance, it is more preferable to set the range as follows in the ninth embodiment. In order to increase the Young's modulus and weather resistance, the SiO2 content is more preferably 60% or more, further preferably 63% or more, and particularly preferably 65% or more. From the viewpoint of improving viscosity, the SiO2 content is more preferably 74% or less, further preferably 72% or less, and particularly preferably 70% or less. The content of Na2O is more preferably 1% or more, even more preferably 2% or more, and particularly preferably 3% or more in order to increase the solubility and adjust the average linear expansion coefficient. Furthermore, since the inclusion of Na2O deteriorates weather resistance, the content is more preferably 15% or less, even more preferably 13% or less, particularly preferably 11% or less, even more preferably 9% or less, and most preferably 7% or less. In order to increase radio wave transmittance, the content of K2O is more preferably 0.5% or more, even more preferably 1% or more, particularly preferably 2% or more, even more preferably 3% or more, and most preferably 4% or more. The content of K2O is more preferably 15% or less, even more preferably 13% or less, particularly preferably 11% or less, even more preferably 9% or less, and most preferably 7% or less.
[0134] The content of Li2O is more preferably 3.5% or more, even more preferably 4% or more, particularly preferably 4.5% or more, and even more preferably 5% or more in order to increase the solubility and Young's modulus and improve the radio wave transmittance. In addition, since the inclusion of Li2O may cause devitrification and phase separation, the content is more preferably 18% or less, even more preferably 16% or less, particularly preferably 14% or less, even more preferably 13% or less, even more preferably 12% or less, and most preferably 10% or less. SrO may be contained to improve solubility and increase radio wave transmittance, and when SrO is contained, its content is preferably 0.5% or more, more preferably 1% or more, and particularly preferably 2% or more. In order to prevent the glass from becoming brittle, the SrO content is more preferably 12% or less, even more preferably 10% or less, particularly preferably 8% or less, even more preferably 6% or less, and most preferably 4% or less. In order to improve the water resistance of the glass, 7Al2O3+3MgO-4Li2O is more preferably -50 or more, even more preferably -40 or more, particularly preferably -35 or more, even more preferably -30 or more, and most preferably -25 or more. In order to increase the radio wave transmittance of the glass, 7Al2O3+3MgO-4Li2O is more preferably -11 or less, even more preferably -12 or less, particularly preferably -13 or less, even more preferably -14 or less, and most preferably -15 or less. In order to increase the radio wave transmittance, Na2O / R2O is more preferably 0.05 or more, even more preferably 0.1 or more, particularly preferably 0.15 or more, even more preferably 0.2 or more, and most preferably 0.25 or more. Na2O / R2O is more preferably 0.95 or less, even more preferably 0.9 or less, particularly preferably 0.8 or less, even more preferably 0.7 or less, even more preferably 0.6 or less, and most preferably 0.5 or less.
[0135] In the ninth embodiment, in order to reduce the viscosity during glass melting and molding and to facilitate production, SiO2+Al2O3 is preferably 50% or more, more preferably 55% or more, particularly preferably 60% or more, even more preferably 65% or more, and most preferably 68% or more. Also, SiO2+Al2O3 is preferably 80% or less, more preferably 78% or less, particularly preferably 76% or less, even more preferably 74% or less, and most preferably 72% or less. In order to lower the glass viscosity during melting and molding and facilitate production, the content of Al2O3 is more preferably 13% or less. Al2O3 is further preferably 11% or less, particularly preferably 9% or less, even more preferably 7% or less, and most preferably 5% or less. In order to ensure weather resistance, Al2O3 is more preferably 1% or more, even more preferably 1.5% or more, particularly preferably 2% or more, especially particularly preferably 2.5% or more, and most preferably 3% or more. In order to increase the radio wave transmittance, K2O / R2O is more preferably 0.05 or more, even more preferably 0.1 or more, particularly preferably 0.15 or more, even more preferably 0.2 or more, and most preferably 0.25 or more. Moreover, K2O / R2O is more preferably 0.95 or less, even more preferably 0.9 or less, particularly preferably 0.7 or less, even more preferably 0.5 or less, and most preferably 0.4 or less. By setting Na2O / R2O and K2O / R2O within a predetermined range, it is preferable because it is easy to increase the radio wave transmittance.
[0136] In the ninth aspect, it is more preferable to lower R2O×MgO in order to increase the radio wave transmittance. R2O×MgO is more preferably 200%. 2 Less than or equal to 100%, more preferably 2 Less than 70%, particularly preferably 2 Less than 50%, more preferably 2 Below 30%, most preferably 2 The following is the result. In order to prevent boron and alkali elements from volatilizing during melting and forming, which leads to deterioration of glass quality, R2O+B2O3 is preferably 25% or less, more preferably 24% or less, more preferably 23% or less, even more preferably 21% or less, even more preferably 19% or less, and most preferably 18% or less. However, if R2O+B2O3 is too low, the glass viscosity during melting and forming may become too high, making production difficult. Therefore, R2O+B2O3 is preferably 1% or more, more preferably 2% or more, even more preferably 4% or more, even more preferably 6% or more, and most preferably 8% or more. In order to prevent boron and alkali elements from volatilizing during melting and forming, which would lead to a deterioration in glass quality, the content of B2O3 is preferably 15% or less, more preferably 12% or less, even more preferably 10% or less, even more preferably 8% or less, and most preferably 6% or less. It may also be contained to improve solubility, and when it is contained, the content of B2O3 is preferably 0.5% or more, more preferably 1% or more, and even more preferably 2% or more. In order to prevent devitrification during glass melting and molding, which leads to deterioration of glass quality, when MgO and CaO are contained, MgO+CaO is preferably 15% or less, more preferably 14% or less, even more preferably 13% or less, even more preferably 12% or less, and most preferably 10% or less. However, if MgO+CaO is too low, the glass viscosity during melting and molding may become too high, making production difficult. Therefore, MgO+CaO is preferably 1% or more, more preferably 2% or more, even more preferably 3% or more, even more preferably 4% or more, and most preferably 5% or more. Furthermore, in order to prevent the glass from becoming brittle and losing strength, or to reduce the weight of the glass sheet, BaO is preferably contained in an amount of 15% or less, more preferably 10% or less, even more preferably 8% or less, particularly preferably 5% or less, even more preferably 3% or less, still more preferably 1% or less, and most preferably substantially none. Similarly, in order to prevent the glass from becoming brittle and losing strength, or to reduce the weight of the glass sheet, the content of SrO+BaO+ZrO2 is more preferably 12% or less, even more preferably 8% or less, particularly preferably 6% or less, even more preferably 4% or less, and most preferably 2% or less. Furthermore, in order to increase radio wave transmittance, the MgO content is more preferably 12% or less, further preferably 8% or less, particularly preferably 5% or less, even more preferably 3% or less, and most preferably 2% or less. In order to improve the solubility and increase the radio wave transmittance, the CaO content is more preferably 0.5% or more, even more preferably 1% or more, particularly preferably 2% or more, even more preferably 3% or more, and most preferably 4% or more. From the viewpoint of suppressing devitrification, the CaO content is more preferably 15% or less, even more preferably 13% or less, particularly preferably 11% or less, even more preferably 9% or less, and most preferably 8% or less. ZrO2 may be contained to improve chemical durability, and when ZrO2 is contained, its content is more preferably 0.5% or more. Since there is a risk of the average linear expansion coefficient becoming large, its content is more preferably 1.8% or less, and further preferably 1.5% or less. From the viewpoint of improving solubility, the content of R2O is more preferably 5% or more, more preferably 6% or more, more preferably 7% or more, even more preferably 8% or more, and particularly preferably 10% or more. On the other hand, in order to improve weather resistance, the content of is more preferably 18% or less, even more preferably 17% or less, even more preferably 15% or less, and particularly preferably 14.5% or less. From the viewpoints of improving solubility and improving radio wave transmittance, the RO content is more preferably 5% or more, even more preferably 7% or more, particularly preferably 10% or more, and most preferably 12% or more. On the other hand, from the viewpoints of improving weather resistance and suppressing devitrification, the RO content is more preferably 19% or less, even more preferably 18% or less, even more preferably 17% or less, particularly preferably 16% or less, and most preferably 15% or less.
[0137] The glass plate according to embodiment 10 of the present invention preferably satisfies the following conditions. The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 0≦Al2O3<1.3 0≦B2O3≦15 0≦MgO≦4.5 0≦CaO≦20 0≦SrO≦4 0≦BaO≦15 0≦Li2O<0.01 0≦Na2O≦14.4 1≦K2O≦16 0≦ZrO2≦2 0.001≦Fe2O3≦1.5 0.001≦TiO2≦5 1.1≦R2O≦18 0≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 0≦7Al2O3+3MgO≦22.6 0.05≦Na2O / R2O≦0.80 0≦PbO<0.001 0≦ZnO≦0.5 Including. By setting the range of the tenth embodiment, it is possible to obtain a glass sheet which exhibits high radio wave transmittance, is easy to mass-produce by the float method, and satisfies the properties required for the desired application.
[0138] In order to increase the radio wave transmittance, it is more preferable to set the range as follows in the tenth embodiment. In order to increase the Young's modulus and weather resistance, the SiO2 content is more preferably 60% or more, further preferably 65% or more, even more preferably 68% or more, and particularly preferably 70% or more. From the viewpoint of improving viscosity, the SiO2 content is more preferably 74% or less, further preferably 73.5% or less, and particularly preferably 73% or less. In order to increase radio wave transmittance, Al2O3 is more preferably less than 1.3%, more preferably 1.2% or less, even more preferably 1.0% or less, and particularly preferably 0.8% or less. In order to increase Young's modulus and weather resistance, Al2O3 is more preferably 0.1% or more, even more preferably 0.2% or more, particularly preferably 0.3% or more, and most preferably 0.5% or more.
[0139] From the viewpoint of improving solubility and weather resistance, the content of MgO is more preferably 0.1% or more, even more preferably 0.25% or more, even more preferably 0.3% or more, even more preferably 0.4% or more, and particularly preferably 0.5% or more. In order to improve radio wave transmittance, the content of MgO is more preferably 4.5% or less, more preferably 4.0% or less, more preferably 3.5% or less, even more preferably 3% or less, even more preferably 2.5% or less, even more preferably 2% or less, particularly preferably 1.5% or less, and most preferably 1% or less. In order to improve solubility and increase radio wave transmittance, the CaO content is preferably 1% or more, more preferably 2% or more, even more preferably 4% or more, particularly preferably 5% or more, even more preferably 6% or more, and most preferably 8% or more. In order to suppress devitrification, the CaO content is more preferably 18% or less, even more preferably 16% or less, particularly preferably 15% or less, even more preferably 14% or less, and most preferably 13% or less.
[0140] BaO may be contained to improve solubility and increase radio wave transmittance, and when BaO is contained, its content is preferably 0.5% or more, more preferably 1% or more, and particularly preferably 2% or more. In order to prevent the glass from becoming brittle, the BaO content is more preferably 12% or less, even more preferably 10% or less, particularly preferably 7% or less, most particularly preferably 5% or less, and most preferably 3% or less. In order to increase the solubility and adjust the average linear expansion coefficient, the content of Na2O is more preferably 0.1% or more, even more preferably 1% or more, particularly preferably 3% or more, even more preferably 5% or more, even more preferably 6% or more, and most preferably 7% or more. Furthermore, since the inclusion of Na2O deteriorates weather resistance, the content is more preferably 13% or less, even more preferably 11% or less, particularly preferably 10% or less, even more preferably 9% or less, and most preferably 8% or less. In order to increase the radio wave transmittance, the content of K2O is more preferably 3% or more, even more preferably 4% or more, particularly preferably 5% or more, even more preferably 6% or more, and most preferably 7% or more. In order to prevent the high-temperature viscosity from becoming too high, the content is more preferably 13% or less, even more preferably 11% or less, particularly preferably 10% or less, even more preferably 9% or less, and most preferably 8% or less.
[0141] ZrO2 may be contained to improve chemical durability, and when ZrO2 is contained, the content is more preferably 0.5% or more. The content of ZrO2 is more preferably 1.8% or less, and further preferably 1.5% or less, since there is a risk of the average linear expansion coefficient becoming large. From the viewpoint of improving solubility, R2O is more preferably 4% or more, more preferably 5% or more, even more preferably 6% or more, even more preferably 7% or more, and particularly preferably 8% or more. On the other hand, in order to improve weather resistance, it is more preferably 17% or less, even more preferably 15% or less, even more preferably 14% or less, particularly preferably 13% or less, particularly preferably 12% or less, especially particularly preferably 11% or less, and most preferably 10% or less. From the viewpoints of improving solubility and radio wave transmittance, RO is more preferably 4% or more, more preferably 5% or more, even more preferably 7% or more, particularly preferably 10% or more, especially particularly preferably 12% or more, and most preferably 12.5% or more. On the other hand, from the viewpoints of improving weather resistance and suppressing devitrification, RO is more preferably 19% or less, even more preferably 18% or less, even more preferably 17% or less, particularly preferably 16% or less, and most preferably 15% or less.
[0142] In order to improve weather resistance and Young's modulus to increase the rigidity of the glass plate, 7Al2O3+3MgO is more preferably 0.5% or more, even more preferably 1% or more, particularly preferably 2% or more, even more preferably 3% or more, and most preferably 5% or more. In order to increase radio wave transmittance, 7Al2O3+3MgO is more preferably 22% or less, even more preferably 20% or less, particularly preferably 18% or less, even more preferably 15% or less, and most preferably 10% or less. In order to increase the radio wave transmittance, Na2O / R2O is more preferably 0.1 or more, more preferably 0.2 or more, more preferably 0.25 or more, even more preferably 0.3 or more, particularly preferably 0.35 or more, even more preferably 0.4 or more, and most preferably 0.45 or more. Na2O / R2O is more preferably 0.75 or less, even more preferably 0.7 or less, particularly preferably 0.65 or less, even more preferably 0.6 or less, and most preferably 0.55 or less. SiO2+Al2O3 is more preferably 50% or more, even more preferably 55% or more, particularly preferably 60% or more, even more preferably 65% or more, and most preferably 68% or more. SiO2+Al2O3 is more preferably 80% or less, even more preferably 78% or less, particularly preferably 76% or less, even more preferably 74.5% or less, even more preferably 74% or less, and most preferably 73% or less.
[0143] It is preferable to lower the R2O×MgO ratio in order to increase the radio wave transmittance. The R2O×MgO ratio is preferably 80%. 2 Less than or equal to 75% 2 Less than or equal to 70%, more preferably 2 Less than 50%, especially preferred 2 Less than 30%, more preferably 2 Below 20%, most preferably 2 The following is the result. In order to prevent boron and alkali elements from volatilizing during melting and forming, which leads to deterioration of glass quality, R2O+B2O3 is preferably 19% or less, more preferably 18% or less, even more preferably 17% or less, even more preferably 16% or less, and most preferably 15% or less. However, if R2O+B2O3 is too low, the glass viscosity during melting and forming may become too high, making production difficult. Therefore, R2O+B2O3 is preferably 2% or more, more preferably 4% or more, more preferably 6% or more, even more preferably 8% or more, even more preferably 10% or more, and most preferably 12% or more. Also in embodiment 10, since the Na2O component in the glass increases relatively to the total alkali amount, particularly in production by the float process, in order to prevent boron and alkali elements from volatilizing during melting and forming, which would lead to a deterioration in glass quality, the B2O3 content is preferably 15% or less, more preferably 10% or less, even more preferably 7% or less, still more preferably 5% or less, even more preferably 3% or less, particularly preferably 2% or less, especially particularly preferably 1% or less, and most preferably substantially none. The glass plate according to the tenth aspect is more preferably 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100. This makes it possible to manufacture the glass plate from glass raw materials that are easily available. In addition, in a composition with low Al2O3 and MgO content, such as the glass of this embodiment, the total amount is more preferably 98.5% or more in order to ensure the weather resistance of the glass plate. The total amount is more preferably 99% or more, and particularly preferably 99.5% or more. Since a colorant, a clarifier, etc. are typically added to a glass plate for a window material, the upper limit of the total amount is even more preferably 99.9%. In addition, in embodiment 10, in order to prevent the glass from becoming brittle and losing strength due to small amounts of Al2O3 and MgO, or to reduce the weight of the glass sheet, the content of SrO is preferably 4% or less, more preferably 2.5% or less, even more preferably 1% or less, and particularly preferably substantially none.
[0144] In order to prevent devitrification during glass melting and forming, which leads to deterioration of glass quality, MgO+CaO is preferably 18% or less, more preferably 16% or less, more preferably 14% or less, even more preferably 13% or less, even more preferably 12% or less, and most preferably 11% or less. However, if MgO+CaO is too low, the glass viscosity during melting and forming may become too high, making production difficult, so MgO+CaO is preferably 1% or more, more preferably 3% or more, even more preferably 4% or more, even more preferably 6% or more, and most preferably 9% or more. Since the glass plate according to embodiment 10 is particularly prone to devitrification, the TiO content is preferably 1.5% or less, more preferably 1% or less, even more preferably 0.5% or less, particularly preferably 0.2% or less, even more preferably 0.1% or less, and most preferably 0.05% or less. The glass plate according to the tenth aspect is preferably made of ZnO at a content of 0.5% or less in order to enable production by the float process. If ZnO is contained, it is not preferable because it forms a Zn-based compound in the float bath and glass defects are easily generated. The content of ZnO is more preferably 0.1% or less, and further preferably is not contained. The glass plate according to this embodiment preferably has an Fe2O3 content of 0.001% to 1.5%. If the Fe2O3 content is less than 0.001%, it may not be possible to use the glass plate in applications requiring heat insulation, and it may be necessary to use expensive raw materials with a low iron content to manufacture the glass plate. Furthermore, when melting glass, heat radiation may reach the bottom surface of the melting furnace more than necessary, which may cause a load on the melting furnace, which is not preferable. The Fe2O3 content is more preferably 0.005% or more, even more preferably 0.01% or more, particularly preferably 0.015% or more, even more preferably 0.02% or more, and most preferably 0.05% or more. If Fe2O3 exceeds 1.5%, heat transfer by radiation may be hindered, and the raw material may not melt easily. Furthermore, if the content of Fe2O3 is too high, the light transmittance in the visible range may decrease (Tv may decrease), and the material may not be suitable for use in automobiles. The content of Fe2O3 is more preferably 1.5% or less, even more preferably 1% or less, even more preferably 0.8% or less, even more preferably 0.6% or less, particularly preferably 0.5% or less, even more preferably 0.4% or less, and most preferably 0.3% or less.
[0145] In any of the above embodiments, the glass plate according to the present invention preferably has a NiO content of 100 mass ppm or less (including 0 mass ppm). In the glass plate according to the present invention, the total content of components other than SiO2, Al2O3, B2O3, MgO, CaO, SrO, BaO, Li2O, Na2O, K2O, TiO2, ZrO2, Fe2O3, and NiO (hereinafter also referred to as "other components") is preferably 5% or less. Examples of other components include Y2O3, Nd2O5, P2O5, GaO2, GeO2, CeO2, MnO2, CoO, Cr2O3, V2O5, Se, Au2O3, Ag2O, ZnO, CuO, CdO, SO3, Cl, F, SnO2, and Sb2O3, and may be metal ions or oxides. The glass plate according to the present invention more preferably has a NiO content of 100 ppm by mass or less (including 0 ppm by mass) and a total content of other components of 5% or less. If NiO is contained, the glass may be broken due to the generation of NiS, so the content is preferably 100 mass ppm or less, more preferably 10 mass ppm or less, and even more preferably NiO is not substantially contained. Other components may be contained in an amount of 5% or less for various purposes (e.g., clarification and coloring). If the content of other components exceeds 5%, there is a risk of negatively affecting the radio wave transmittance. The content of other components is more preferably 3% or less, more preferably 2% or less, more preferably 1.5% or less, even more preferably 1% or less, particularly preferably 0.5% or less, even more preferably 0.3% or less, and most preferably 0.1% or less. In addition, in order to prevent effects on the environment and human body, the content of As2O3 and PbO is more preferably less than 0.001%, and most preferably substantially not contained. SO3 is used as a fining agent and can contribute to defoaming. When SO3 is used, it can be contained in glass by using sulfate as a raw material, and the content of SO3 when it is contained is preferably 0.01% or more, more preferably 0.02% or more, more preferably 0.04% or more, particularly preferably 0.08% or more, and most preferably 0.1% or more. If it is contained in a large amount, there is a risk of causing the above-mentioned amber coloring, so it is preferably 1% or less, more preferably 0.8% or less, even more preferably 0.6% or less, and most preferably 0.5% or less. Sb2O3 acts as a fining agent like SO3, but in order to prevent adverse effects on the environment and human body, it is more preferable that the content be 0.5% or less, even more preferably 0.2% or less, even more preferably 0.1% or less, particularly preferably 0.05% or less, especially particularly preferably 0.01% or less, and it is most preferable that the content be substantially zero. CeO2 acts as an oxidizing agent and can control the amount of FeO. It can also block ultraviolet rays, so it can prevent deterioration of interior materials caused by ultraviolet rays. When CeO2 is included, the content is preferably 0.004% or more, more preferably 0.01% or more, even more preferably 0.05% or more, and particularly preferably 0.1% or more. In order to prevent an increase in manufacturing costs, it is preferably 1% or less, more preferably 0.5% or less, and particularly preferably 0.3% or less. Cr2O3 acts as an oxidizing agent and can control the amount of FeO. When Cr2O3 is contained, the content is preferably 0.002% or more, more preferably 0.004% or more. Since Cr2O3 has color in the visible range, there is a risk of reducing the transmittance in the visible range. It is preferably 1% or less, more preferably 0.5% or less, particularly preferably 0.3% or less, and most preferably 0.1% or less. SnO2 acts as a reducing agent and can control the amount of FeO. When SnO2 is contained, the content is preferably 0.01% or more, more preferably 0.04% or more, even more preferably 0.06% or more, and particularly preferably 0.08% or more. In order to suppress defects derived from SnO2 during production, the content is preferably 1% or less, more preferably 0.5% or less, particularly preferably 0.3% or less, and most preferably 0.2% or less. Furthermore, since P2O5 is likely to cause defects in the glass in the float bath during production by the float process, the content is more preferably 1% or less, even more preferably 0.5% or less, particularly preferably 0.1% or less, and even more preferably less than 0.001%.
[0146] The glass plate according to the present invention preferably has a dielectric loss tan δ of 0.001 or more and 0.019 or less at a frequency of 35 GHz. It is particularly preferable to reduce the dielectric loss tan δ of the glass material, since it can increase the radio wave transmittance. Tan δ is preferably 0.019 or less, more preferably 0.017 or less, even more preferably 0.015 or less, particularly preferably 0.013 or less, even more preferably 0.010 or less, and most preferably 0.008 or less. From the viewpoint of radio wave transmittance, there is no lower limit to the desirable dielectric loss, but if tan δ is too low, the SiO2 component tends to be too high, and the solubility of the glass may decrease. Therefore, tan δ is preferably 0.0015 or more, more preferably 0.003 or more, even more preferably 0.004 or more, particularly preferably 0.005 or more, even more preferably 0.007 or more, and most preferably 0.0075 or more.
[0147] The glass plate according to the present invention preferably has a thickness of 1 mm or more and 36 mm or less. If the thickness is less than 1 mm, it is difficult to obtain rigidity and may not be suitable for practical use. The thickness of the glass plate according to the present invention is more preferably 1.2 mm or more, even more preferably 1.8 mm or more, particularly preferably 2.4 mm or more, even more preferably 2.8 mm or more, and most preferably 3.7 mm or more. If the thickness exceeds 36 mm, the advantage of the material having high radio wave transmittance may not be fully utilized in practical use. The thickness is more preferably 24 mm or less, even more preferably 12 mm or less, particularly preferably 10 mm or less, even more preferably 8 mm or less, and most preferably 7 mm or less.
[0148] This thickness may be the total thickness of the laminated glass. For example, two different glass sheets according to the present invention may be laminated to the above thickness. The glass sheet according to the present invention may be used in combination with another glass sheet, i.e., stacked or adjacent to another glass sheet. The glass sheet having the above-mentioned specific composition can ensure the radio wave transmittance specified in this specification even when it is stacked with a glass sheet having a different composition. In other words, only a part of the layers of the laminated glass may have the above-mentioned specific composition. The glass sheet according to the present invention may be used by laminating it with a transparent resin other than glass.
[0149] In another aspect of the present specification, there is provided a window comprising a glass pane according to the above embodiment.
[0150] In this specification, the term "window" refers to a glass sheet used to separate the interior and exterior of a vehicle or building or one room from an adjacent room and to provide visibility, surrounded by a non-glass material. "Vehicle" may include any vehicle or means of transportation having a room surrounded by a wall (which may include a window), such as an automobile, train, carriage, ship, airplane, helicopter, cable car, or Ferris wheel. Similarly, "building" may include any building having a room surrounded by a wall (which may include a window), such as a house, office building, store, warehouse, factory, or booth. The non-glass material surrounding the glass sheet in the window may be, for example, but is not limited to, metal, wood, concrete, stone, ceramics, brick, plastic, carbon fiber, or any mixture thereof. The non-glass material surrounding the glass sheet is typically the body frame or door frame of an automobile, or the material or window frame of a wall, ceiling, floor, or door in a building. The entire door, the entire wall, the entire ceiling, or the entire floor may be made of a window.
[0151] The glass sheets provided in the window according to the present invention are typically 10,000 mm 2 The windows may have the above areas, but may also be constructed by arranging several glass panes of smaller areas side by side. The glass pane according to the invention may be laminated and fitted with other glass panes or transparent materials in the windows according to the invention.
[0152] In one embodiment, the window is an automobile window. That is, the window may be an automobile windshield, rear windshield, front door glass, rear door glass, side glass, roof glass, etc. The thickness of the glass plate provided in the automobile window is preferably 1.2 mm or more, more preferably 2 mm or more, further preferably 2.8 mm or more, even more preferably 3.2 mm or more, and most preferably 3.7 mm or more. In the case of a windshield or a front door glass, the visible light transmittance Tv_A (JIS R 3106:1998) of the glass plate provided in the automobile window is preferably 72% or more in terms of a 3.85 mm thickness. In the case of a glass plate other than a windshield or a front door glass, Tv_A is usually 30 to 92%, depending on the application.
[0153] In one embodiment, the automobile window can be provided with an information acquisition device that acquires information from outside the vehicle by irradiating and / or receiving light, has at least one information acquisition area that faces the information acquisition device and through which light passes, and has an outer glass plate, an inner glass plate, and an intermediate film that is arranged between these glass plates. It is particularly preferable to use the automobile window for a windshield. The automobile window may be laminated glass or tempered glass. The tempered glass may be physically tempered glass or chemically tempered glass. It is preferable that the wavelength of light irradiated and / or received on the automobile window is in the range of 700 to 1650 nm, since commercially available laser radars and infrared cameras can be used. Furthermore, it is preferable that the transmittance of the information acquisition area at wavelengths of 700 to 1650 nm is 80 to 92%, since this facilitates light detection by the information acquisition device. The transmittance is more preferably 83% or more, even more preferably 86% or more, particularly preferably 88% or more, even more preferably 89% or more, and most preferably 90% or more. Furthermore, if the transmittance at wavelengths of 700 to 1650 nm is too high, there is a risk of the heat shielding properties being deteriorated, so the transmittance is more preferably 91.5% or less, and even more preferably 91% or less.
[0154] In one embodiment, the automobile window can accommodate an information acquisition device that acquires information from outside the vehicle by irradiating and / or receiving radio waves, has at least one information acquisition area that faces the information acquisition device and through which the radio waves pass, and has an outer glass sheet, an inner glass sheet, and an intermediate film that is arranged between these glass sheets. It is particularly preferable to use the automobile window for a front glass (windshield). If the frequency of the radio waves irradiated and / or received by the automobile window is in the range of 2 to 100 GHz, it is preferable because a commercially available radar device can be used. More preferably, it is 20 GHz or more, even more preferably, 50 GHz or more, and particularly preferably, 60 GHz or more. Furthermore, if at least one of the outer glass and the inner glass used in the information acquisition area has a radio wave transmittance of 20 to 84% at a frequency of 100 GHz converted to a thickness of 18 mm, it is preferable because radio wave detection by the information acquisition device becomes easy. The radio wave transmittance is more preferably 22% or more, even more preferably 25% or more, even more preferably 29% or more, particularly preferably 33% or more, even more preferably 37% or more, and most preferably 40% or more. Moreover, if the radio wave transmittance is too high, it becomes difficult to manufacture the glass, so it is more preferably 80% or less, more preferably 70% or less, more preferably 60% or less, even more preferably 55% or less, even more preferably 50% or less, particularly preferably 45% or less, even more preferably 43% or less, and most preferably 41% or less.
[0155] In one embodiment, it is more preferable that the device is capable of both emitting and / or receiving light and emitting and / or receiving radio waves.
[0156] In one embodiment, the window is a building window, i.e. the window is arranged in the wall, door, ceiling, roof or floor of a building. The thickness of the glass plate of the building window is preferably 2 mm or more, more preferably 4 mm or more, even more preferably 6 mm or more, particularly preferably 8 mm or more, even more preferably 10 mm or more, and most preferably 12 mm or more.
[0157] The glass plate according to the embodiment of the present invention, or the glass plate provided in the window according to the embodiment of the present invention, preferably has a length of 30 mm or more in the polarization direction of radio waves. The polarization direction may be, for example, a direction perpendicular to the plumb line and parallel to the glass plate surface, or a direction parallel to the plumb line and parallel to the glass plate surface. For example, a glass plate provided in a flat window installed perpendicular to the ground plane may have the above-mentioned length in the lateral (horizontal) direction or the longitudinal (vertical) direction. If the glass plate has a sufficient length in the polarization direction, it becomes easier to transmit and receive radio waves from radar or mobile phones.
[0158] In another aspect of the present specification, there is provided a wireless communication device including the glass plate according to the above embodiment.
[0159] In this specification, the term "wireless communication device" refers to an electronic device medium that utilizes wireless communication. The term "wireless communication device" may include a mobile phone, a tablet, a personal computer, a watch, glasses, and the like. The term "wireless communication device" in this specification has a surface member and a back member, and the glass plate according to the above embodiment may be used for at least a part of the surface member or the back member. In addition, typically, a housing part that holds the surface member and the back member is included. An element having a display function, an electric circuit board for driving the element, and the like may be included inside the space surrounded by the surface member, the back member, and the housing part. Examples of the element having a display function include a liquid crystal display element and an organic EL element. Information can be displayed by an element having a display function at least on the surface member side. Information may also be displayed by an element having a display function from the back member side depending on the application. The surface member and the back member can be shaped according to the application, and may be flat or curved. The front and rear members may have holes for a speaker, operation buttons, a camera lens, etc. Typically, the front member has holes for a speaker and operation buttons, and the rear member has a hole for a camera lens. The materials for the front surface member, back surface member and housing portion can be, for example, glass, crystallized glass, phase-separated glass, metal, wood, stone, ceramics, plastic, carbon fiber, or any mixture or combination of these laminated materials.
[0160] The glass plate included in the wireless communication device according to the present invention may be laminated and fitted with another glass plate or transparent material, or may be a chemically strengthened glass plate. The glass plate provided in the wireless communication device according to the present invention may be used for both the front and rear members of the wireless communication device, or for only one of them. The glass plate provided in the wireless communication device according to the present invention has a radio wave transmittance of 20% or more at a frequency of 100 GHz converted to a thickness of 18 mm, and therefore is unlikely to be a barrier to transmission and reception when the wireless communication device is used. When provided in a wireless communication device, this radio wave transmittance is preferably 27% or more, more preferably 28% or more, even more preferably 29% or more, particularly preferably 30% or more, and most preferably 32% or more. In addition, when both the front and rear members are provided with the glass plate according to the above embodiment, the difference between the radio wave transmittance at a frequency of 100 GHz converted to a thickness of 18 mm of the glass plate used in the front member and the radio wave transmittance at a frequency of 100 GHz converted to a thickness of 18 mm of the glass plate used in the rear member is preferably 4% or more. If the difference in radio wave transmittance is 4% or more, radio waves can be transmitted and received through the member with the higher radio wave transmittance of the front and rear members, and radio waves can be suppressed from being transmitted and received from the other member. For example, when a speaker or a microphone is present on the front member side, the front member side is the side of the human head, so that the radio waves reaching the human head can be weakened by using a glass plate with a low radio wave transmittance on the front member side, and radio waves can be transmitted and received by using a glass plate with a high radio wave transmittance on the rear member side.
[0161] In one embodiment, the wireless communication device is provided with an antenna as a device for transmitting and receiving radio waves. The antenna may be placed close to or in contact with the glass plate, or may be formed inside the glass plate. This can improve the transmission and reception sensitivity of the antenna. In addition, the antenna is preferably capable of transmitting and receiving electromagnetic waves with a frequency of 1.0 GHz or more. The frequency of the radio waves transmitted and received by the antenna is preferably 2.4 GHz or more, more preferably 5 GHz or more, even more preferably 10 GHz or more, particularly preferably 15 GHz or more, and most preferably 25 GHz or more. There is no particular upper limit, but in view of the applications of the glass of the present application, the frequency used is 100 GHz or less, preferably 90 GHz or less.
[0162] In one embodiment, the thickness of the glass plate provided in the wireless communication device, when used as a part or the whole of the back member, is preferably 4 mm or less, more preferably 2.5 mm or less, even more preferably 1.5 mm or less, particularly preferably 1.1 mm or less, even more preferably 0.9 mm or less, and most preferably 0.7 mm or less. On the other hand, since the strength may be weakened if the glass plate is thin, it is more preferable that the thickness is 0.5 mm or more. The thickness may not be uniform and may have a distribution, and can be determined according to the application. Here, when the thickness of the glass plate has a distribution, the thickness of the thickest part is defined as the "thickness of the glass plate" (the same applies hereinafter in this specification).
[0163] In one embodiment, the thickness of the glass plate provided in the wireless communication device, when used as a part or the whole of the surface member, is preferably 2.5 mm or less, more preferably 1.5 mm or less, even more preferably 1.3 mm or less, particularly preferably 1.1 mm or less, even more preferably 0.9 mm or less, and most preferably 0.7 mm or less. On the other hand, since the strength may be weakened if the glass plate is thin, it is more preferable that the thickness is 0.5 mm or more. The thickness does not have to be uniform and may have a distribution, and can be determined according to the application.
[0164] The visible light transmittance of the glass plate installed in the wireless communication device may be adjusted according to the application, but the visible light transmittance of the glass plate used on the side on which information is displayed is more preferably 60% or more when converted into a 3.85 mm thickness value. The present disclosure includes the following embodiments. [1] A glass plate with a radio wave transmittance of 20% or more at a frequency of 100 GHz when converted to an 18 mm thickness. [2] The glass plate according to [1], which has a radio wave transmittance of 25% or more at a frequency of 100 GHz when converted into a glass plate having a thickness of 18 mm. [3] The glass plate according to [1] or [2], which has a radio wave transmittance of 84% or less at a frequency of 100 GHz when converted into a glass plate having a thickness of 18 mm. [4] When a plane wave with a frequency of 10 GHz and an electric field strength of 1 V / m is incident on a glass plate with a thickness of 1.2 λ from a wave source 2 λ away from the aperture, the electric field strength at an observation point 10 λ away from the aperture is y (V / m), and the aperture area S (mm 2 ) into λ 2 The glass plate according to any one of [1] to [3], wherein, when a value obtained by dividing by x is taken as x, a linear approximation is y>(0.0607×x). [5] The glass plate according to any one of [1] to [4], wherein an exponential approximation is y'>exp(-0.081×x'), where y' is an approximate transmittance at a frequency of 100 GHz and x' (mm) is a thickness of the glass plate. [6] The relationship between frequency x'' and radio wave transmittance y'' at frequencies between 6 and 20 GHz, converted to an 18 mm thickness, is y''=[constant 1]×e [定数2]×x’’ In the exponential approximation to the function y''>0.8619e -0.015x’’ The glass plate according to any one of [1] to [5], [7] Area is 900mm 2 The glass plate according to any one of [1] to [6] above. [8] The specific gravity is 2.40 to 3.00, the Young's modulus is 60 GPa to 100 GPa, and the average linear expansion coefficient at 50°C to 350°C is 35×10 -7 ~120×10 -7 / °C. The glass plate according to any one of [1] to [7]. [9] The glass plate according to any one of [1] to [8], wherein the amount of Na2O eluted in a water resistance test is 0.001 mg to 0.6 mg.
[10] T2 is 1750℃ or less, T4 is 1350℃ or less, T4-T L The glass plate according to any one of [1] to [9], wherein the glass plate has a temperature of −150° C. or higher. (However, T2 has a glass viscosity of 10 2 (dPa s), T4 is the temperature at which the glass viscosity is 10 4 (dPa s), T L is the liquidus temperature of glass.)
[11] Glass transition temperature T g The glass plate according to any one of [1] to
[10] , wherein the heating temperature is 400° C. to 750° C.
[12] The glass plate according to any one of [1] to
[11] , having a visible light transmittance Tv_A converted to a plate thickness of 3.85 mm of 30 to 92%.
[13] The glass plate according to any one of [1] to
[12] , having a solar transmittance Te converted to a plate thickness of 3.85 mm of 35 to 91%.
[14] The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 0≦Al2O3≦9 0≦B2O3≦15 0≦MgO≦15 0≦CaO≦20 0≦SrO≦15 0≦BaO≦15 0≦Li2O<0.01 1.2≦Na2O≦15.6 3.5≦K2O≦12.5 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 4.7≦R2O≦19.5 0≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 42<7Al2O3+3MgO≦66 0.25≦Na2O / R2O≦0.8 R2O+B2O3≦23 0≦PbO<0.001 The glass plate according to any one of [1] to
[13] ,
[15] The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 0≦Al2O3≦6 0≦B2O3≦15 0≦MgO≦14 0≦CaO≦20 0≦SrO≦15 0≦BaO≦15 0≦Li2O<0.01 4≦Na2O≦17 1.9≦K2O≦14.2 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦3 5.9≦R2O≦20 0≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 23.5<7Al2O3+3MgO≦42 0.22≦Na2O / R2O≦0.85 R2O×MgO≦66 55≦SiO2+Al2O3≦76 0≦PbO<0.001 The glass plate according to any one of [1] to
[13] ,
[16] The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 1.3≦Al2O3≦3.35 0≦B2O3≦15 0≦MgO≦4.8 0≦CaO≦20 0≦SrO≦4 0≦BaO≦15 0≦Li2O<0.01 0.1≦Na2O≦16 1≦K2O≦16 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦1.5 1.1≦R2O≦20 0≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 0≦7Al2O3+3MgO≦23.5 0.05≦Na2O / R2O≦0.8 0≦R2O+B2O3≦22 0≦PbO<0.001 0≦ZnO≦8 The glass plate according to any one of [1] to
[13] ,
[17] The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 1.44≦Al2O3≦9 0≦B2O3≦2 0≦MgO≦15 0≦CaO≦20 0≦SrO≦15 0≦BaO≦1 0.01≦Li2O≦19.1 0≦Na2O≦16 0.9≦K2O≦16 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 0.91≦R2O≦20 0≦RO≦20 98≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 10<7Al2O3+3MgO-4Li2O≦66 0≦Na2O / R2O≦0.8 0≦PbO<0.001 The glass plate according to any one of [1] to
[13] ,
[18] The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 0≦Al2O3≦7.8 0≦B2O3≦2 0≦MgO≦11.8 2≦CaO≦20 0≦SrO≦15 0≦BaO≦1 2.5≦Li2O≦19.52 0.15≦Na2O≦17.17 0.33≦K2O≦16.5 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 2.98≦R2O≦20 2≦RO≦20 98≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 -10<7Al2O3+3MgO-4Li2O≦10 0.05≦Na2O / R2O≦0.85 0.11≦K2O / R2O≦0.83 0≦PbO<0.001 The glass plate according to any one of [1] to
[13] ,
[19] The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 0≦Al2O3≦5.5 0≦B2O3≦2 0≦MgO≦10.5 0≦CaO≦20 0≦SrO≦15 0≦BaO≦15 2.5≦Li2O≦20 0≦Na2O≦18.5 0≦K2O≦18.5 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 2.5≦R2O≦20 0≦RO≦20 98≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 -60≦7Al2O3+3MgO-4Li2O≦-10 0≦PbO<0.001 The glass plate according to any one of [1] to
[13] ,
[20] The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 1.44≦Al2O3≦9 0.5≦B2O3≦13 0≦MgO≦15 0≦CaO≦20 0≦SrO≦15 0≦BaO≦1 0.01≦Li2O≦19.1 0≦Na2O≦16 0.9≦K2O≦16 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 0.91≦R2O≦20 0≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 10<7Al2O3+3MgO-4Li2O≦66 0≦Na2O / R2O≦0.8 0≦PbO<0.001 0≦ZnO≦3 The glass plate according to any one of [1] to
[13] , [twenty one] The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 1≦Al2O3≦7.8 0.5≦B2O3≦15 0≦MgO≦11.8 2≦CaO≦20 0≦SrO≦15 0≦BaO≦1 4.25≦Li2O≦19.15 0.25≦Na2O≦15.15 0.60≦K2O≦15.5 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 5.10≦R2O≦20 2≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 -10<7Al2O3+3MgO-4Li2O≦10 0.05≦Na2O / R2O≦0.95 0.11≦K2O / R2O≦0.9 0≦PbO<0.001 The glass plate according to any one of [1] to
[13] , [twenty two] The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 0.5≦Al2O3≦15 0≦B2O3≦15 0≦MgO≦15 0≦CaO≦20 0≦SrO≦15 0≦BaO≦15 3.4 <Li2O≦20 0≦Na2O≦16.6 0≦K2O≦16.6 0≦ZrO2≦2 0.001≦Fe2O3≦5 0.001≦TiO2≦5 3.4 <R2O≦20 1≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 -60≦7Al2O3+3MgO-4Li2O≦-10 0≦PbO<0.001 The glass plate according to any one of [1] to
[13] , [twenty three] The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO2≦75 0≦Al2O3<1.3 0≦B2O3≦15 0≦MgO≦4.5 0≦CaO≦20 0≦SrO≦4 0≦BaO≦15 0≦Li2O<0.01 0≦Na2O≦14.4 1≦K2O≦16 0≦ZrO2≦2 0.001≦Fe2O3≦1.5 0.001≦TiO2≦5 1.1≦R2O≦18 0≦RO≦20 85≦SiO2+Al2O3+MgO+CaO+SrO+BaO+Li2O+Na2O+K2O+Fe2O3+TiO2≦100 0≦7Al2O3+3MgO≦22.6 0.05≦Na2O / R2O≦0.80 0≦PbO<0.001 0≦ZnO≦0.5 The glass plate according to any one of [1] to
[13] , [twenty four] A x radio wave transmittance is 0.0225m 2 %~8400m 2 %, where A is the area of the glass plate (m 2The glass plate according to any one of [1] to
[23] , [twenty five] The glass plate according to any one of [1] to
[24] , having a radio wave transmittance / t of 0.7% / mm to 84% / mm, where t is the thickness (mm) of the glass plate.
[26] A window comprising the glass plate according to any one of [1] to
[25] .
[27] The window according to
[26] , which is for use in automobiles or building materials.
[28] A wireless communication device comprising the glass plate according to any one of [1] to
[25] . EXAMPLES
[0165] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the present invention is not limited to these examples.
[0166] [Preparation of glass plate samples] Glass plates having the compositions (units: mol%) shown in Tables 1-1 to 1-28 below were produced by a conventional method known to those skilled in the art. Specifically, the raw materials were placed in a platinum crucible and melted at 1550°C for 2 hours to obtain the indicated glass compositions, and then the molten liquid was poured onto a carbon plate and slowly cooled to obtain a glass plate. Both sides of the obtained plate were polished to obtain a glass plate having a thickness of about 30 mm.
[0167] The method for determining the values shown in Tables 1-1 to 1-28 is described below. (1) Average linear expansion coefficient (α) at 50 to 350°C: The average linear expansion coefficient (α) was measured using a thermal expansion meter (TMA) and determined in accordance with JIS R3102 (1995). (2) Glass transition temperature (Tg): The glass transition temperature (Tg) was a value measured using TMA in accordance with JIS R3103-3 (2001). (3) Specific gravity (d): The specific gravity (d) was measured by the Archimedes method using a glass block of about 20 g containing no bubbles cut out from a glass plate. (4) Viscosity: The viscosity was measured using a rotational viscometer, and the viscosity η was 10 2 The temperature T2 (reference temperature for solubility) at which the viscosity becomes dPa·s and the viscosity η of 10 4 The temperature T4 (reference temperature for formability) at which the viscosity reached dPa·s was measured. (5) Liquidus temperature (T L ): Platinum dishes containing 5 g of glass chunks cut from a glass plate were placed in electric furnaces at different temperatures higher than the glass transition point, and after 17 hours, the plates were removed from the furnaces and cooled. After cooling, the glass chunks were checked for the presence or absence of precipitation on their surface and inside, and the lowest temperature at which no crystals precipitated after 17 hours of holding was recorded as the liquidus temperature. (6)Young's modulus (E): Young's modulus E was measured at 25°C by the ultrasonic pulse method (Olympus, DL35). (7)Water resistance: The amount of Na2O dissolved (mg) was measured according to JIS R 3502 (1995). (8)Visible light transmittance (Tv_A): The glass plate was processed into a rectangular parallelepiped with a length of 30.0 mm, a width of 30.0 mm, and a thickness of 3.85 mm, and the 30.0 mm x 30.0 mm surface was polished to a mirror finish. The transmittance was measured using a spectrophotometer in accordance with JIS R 3106:1998, and the visible light transmittance Tv_A was calculated. The spectrophotometer used was a Hitachi High-Technologies Corporation U4100 spectrophotometer. The weighting coefficient was the value for a standard A light source and a 2-degree visual field. It is expressed as a value converted to a plate thickness of 3.85 mm. Here, the value converted to a plate thickness of 3.85 mm is obtained by measuring the refractive index of the glass plate whose transmittance was measured, and calculating the reflectance of the glass plate from the refractive index using the Sellmeyer equation, and converting the value of the glass plate (here, visible light transmittance Tv_A) to a value for a plate thickness of 3.85 mm, taking multiple reflections into account. When the visible light transmittance Tv_A was 30 to 92%, it was marked with "O", and when it was greater than 92% or less than 30%, it was marked with "X". (9)Solar transmittance (Te): For Te, the transmittance was measured using a spectrophotometer in accordance with ISO-13837A:2008, and the solar transmittance Te was calculated. The value is expressed as a converted value for a plate thickness of 3.85 mm. Solar transmittance Te of 35 to 91% was indicated by "○", and solar transmittance Te of greater than 91% or less than 35% was indicated by "×". (10) Ultraviolet transmittance (Tuv): Tuv is defined in ISO-9050:2003. (11) Transmittance at 905 nm wavelength, transmittance at 1550 nm wavelength Measured using a spectrophotometer. Values are expressed as converted values for a plate thickness of 3.85 mm. (12) FeO content The crushed glass was decomposed at room temperature using a mixture of hydrofluoric acid and hydrochloric acid, and a certain amount of the decomposition liquid was dispensed into a plastic container. A 2,2'-dipyridyl solution and an ammonium acetate buffer solution were quickly added to the container to extract the Fe 2+ Only the FeO was allowed to develop color. The color-developing solution was adjusted to a certain amount with ion-exchanged water, and the absorbance at a wavelength of 522 nm was measured with an absorptiometer. The concentration was then calculated from a calibration curve made using the standard solution, and the amount of FeO was calculated. The FeO in the table is the amount of FeO converted to Fe2O3. (13)Radio wave transmittance The radio wave transmittance at 18 mm thickness and 100 GHz, constant 1 in the exponential approximation equation (converted to 18 mm thickness) of the relationship between frequency and radio wave transmittance, and constant 2 in the exponential approximation equation (converted to 18 mm thickness) of the relationship between frequency and radio wave transmittance were calculated by the method described above. Here, the radio wave transmittance at 18 mm thickness and 100 GHz was obtained by performing exponential approximation as described above. The relative dielectric constant and dielectric loss of the glass used in the calculation were measured by the cavity resonance method. (14) Radio wave transmission rate of laminated glass Both sides of the glass plate were further polished to obtain a glass plate having a thickness of 2.0 mm. The two glass plates having a thickness of 2.0 mm were laminated together via an adhesive layer made of polyvinyl butyral (interlayer: PVB) and pre-bonded under reduced pressure. The laminated glass was then heated and pressurized in an autoclave chamber to obtain a laminated glass. The adhesive layer of the laminated glass obtained had a thickness of 0.7 mm. The amount of radio wave transmission through the obtained laminated glass was measured using the free space method. Antennas were placed facing each other, and the obtained laminated glass was placed between them. The amount of radio wave transmission through the laminated glass was measured at a 100 mm diameter opening, with the absence of the laminated glass taken as 0 dB. The frequency range was 65 to 85 GHz. FIG. 4 is a graph showing the measured values of the radio wave transmission amount of the laminated glass of Comparative Example 1 and the calculated values of the radio wave transmission amount obtained by exponential approximation. It was confirmed that the measured values and the calculated values matched well. Similar calculations were performed for Examples 3, 4, 11, and 25. FIG. 5 is a graph showing the measured values of the radio wave transmission amount of the laminated glass of Comparative Example 1, Example 3, Example 4, Example 11, and Example 25 and the calculated values of the radio wave transmission amount obtained by exponential approximation. The frequency of this maximum value can be adjusted by the dielectric constant and the thickness of the glass. It was confirmed that the measured values and the calculated values matched well.
[0168] In the table, "-" indicates that no measurement was performed, and values calculated from the composition are shown in italics.
[0169] [Table 1-1]
[0170] [Table 1-2]
[0171] [Table 1-3]
[0172]
Table 1-4
[0173]
Table 1-5
[0174]
Table 1-6
[0175]
Table 1-7
[0176]
Table 1-8
[0177]
Table 1-9
[0178]
Table 1-10
[0179]
Table 1-11
[0180]
Table 1-12
[0181]
Table 1-13
[0182]
Table 1-14
[0183]
Table 1-15
[0184]
Table 1-16
[0185]
Table 1-17
[0186]
Table 1-18
[0187]
Table 1-19
[0188]
Table 1-20
[0189]
Table 1-21
[0190]
Table 1-22
[0191]
Table 1-23
[0192]
Table 1-24
[0193] [Table 1-25]
[0194] [Table 1-26]
[0195] [Table 1-27]
[0196] [Table 1-28]
[0197] [Study of calculation model for radio wave transmittance] The glass plate shown as Comparative Example 1 in Table 1 was used to confirm the discrepancy between the measured radio wave transmittance and the calculation model. The actual measured values were obtained by measurement using the free space method from a 30 cm x 30 cm glass plate. The calculation model of the free space method is a calculation model used in simulations in CST's Microwave Studio 2016 electromagnetic field simulator. The basic conditions of the simulation are as described above in this specification. As a result of the study, it was revealed that by adjusting the value of tan δ input in the calculation model to an accuracy of up to three decimal places, the calculation model in the high frequency range (e.g., 50 GHz or higher) is optimized, and a more accurate fitting to the actual measured values can be obtained for glass plates of different thicknesses (e.g., 5 mm and 10 mm).
[0198] Using this optimized calculation model, the radio wave transmittance or approximate transmittance of the comparative example (conventional glass plate) was determined and compared with those of Examples 1 to 249. As a result, it was found that the radio wave transmittance of the glass of the examples at a frequency of 100 GHz converted to a thickness of 18 mm was 20% or more in all cases, which was superior to the comparative examples. 2 It was clear that both the value of radio wave transmittance × A at 2.0 mm and the value of radio wave transmittance / thickness t at a thickness of 3.85 mm were superior to those of the comparative example.
[0199] [Comparison of radio wave transmittance] 2A to 2D are graphs showing the electric field strength ratios of the glass plates of the Comparative Example and Examples 1 to 20 at a thickness of 18 mm. The black curve shows the electric field strength ratio of the Comparative Example, and the black dotted line shows the exponential approximation ([radio wave transmittance]=[constant 1]×e [定数2]×[周波数] The graph shows the radio wave transmittance calculated by approximating the function of the above formula (i.e., "exponential approximation of the relationship between frequency and electric field strength ratio"). Similarly, each of the gray curves represents the electric field strength ratio of each example, and the gray dotted lines represent the radio wave transmittance calculated by the exponential approximation corresponding to each of the gray curves. It can be seen that the glass sheets of the examples have generally high radio wave transmittance in the gigahertz frequency band.
[0200] Figures 3A to 3D show approximate transmittances at representative frequencies calculated based on the exponential approximation equations obtained in Figures 2A to 2D. Figure 3A corresponds to Figure 2A, Figure 3B corresponds to Figure 2B, Figure 3C corresponds to Figure 2C, and Figure 3D corresponds to Figure 2D, and shows approximate transmittances for the Comparative Example and Examples 1 to 20. It can be seen that all of the Examples have radio wave transmission characteristics that are significantly improved over the Comparative Example. Moreover, the glass plates of Examples 21 to 249 are within any of the composition ranges described in the above-mentioned 10 types of embodiments, and therefore have high radio wave transmittance. The dielectric loss tan δ at a frequency of 35 GHz was 0.001 or more and 0.019 or less for the glasses of Examples 5 to 7 and 17 to 20, 0.001 or more and 0.013 or less for the glasses of Examples 2, 4, 8 to 10, 12, 14, 16, and 21 to 23, and 0.001 or more and 0.011 or less for the glasses of Examples 1, 3, 11, 13, 15, and 24. The results of Example 3, Example 4, Example 11, and Example 25 show that the laminated glasses of the Examples have higher radio wave transmittance than the laminated glasses of the Comparative Examples. [Industrial Applicability]
[0201] The glass plate of the present invention can be widely used as a window material in buildings and vehicles in which the use of radio wave devices such as mobile phones and radars is anticipated. Furthermore, the glass plate of the present invention can be suitably used as a glass plate for wireless communication devices that use radio waves with high frequencies of 1.0 GHz or more. The entire contents of the specifications, claims, abstracts and drawings of Japanese Patent Application No. 2017-90141 filed on April 28, 2017 and Japanese Patent Application No. 2017-140687 filed on July 20, 2017 are hereby incorporated by reference as the disclosure of the specification of the present invention. [Explanation of symbols]
[0202] 10 frames, 20 apertures, 30 sources, 40 observation points
Claims
1. The radio wave transmittance at a frequency of 100 GHz converted to an 18 mm thickness is 20% or more, The content of each component is as follows, expressed as mole percentage based on oxide: 55≦SiO 2 ≦75 1.44≦Al 2 O 3 ≦9 0.5≦B 2 O 3 ≦13 0≦MgO≦15 0≦CaO≦20 0≦SrO≦15 0≦BaO≦1 0.01≦Li 2 O≦19.1 0≦Na 2 O≦16 0.9≦K 2 O≦16 0≦ZrO 2 ≦2 0.001≦Fe 2 O 3 ≦5 0.001≦TiO 2 ≦5 0.91≦R 2 O≦20 0≦RO≦20 85≦SiO 2 +AS 2 O 3 - 2 O+1 2 O+K 2 O+Fe 2 O 3 +T&O 2 ≦100 50≦SiO 2 +Al 2 O 3 ≦75 <h2 style=";text-align:left;direction:ltr">15<7Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> +3MgO-4Li<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O≦66 0≦Na 2 O / R 2 O≦0.8 0≦PbO<0.001 0≦ZnO≦3 R 2 O+B 2 O 3 ≦20 Including, RO represents the total content of MgO, CaO, SrO, and BaO; R 2 O is Li 2 O, Na 2 O and K 2 A glass plate showing the total O content.
2. 2. The glass plate according to claim 1, which has a radio wave transmittance of 25% or more at a frequency of 100 GHz when converted into a glass plate having a thickness of 18 mm.
3. 3. The glass plate according to claim 1, which has a radio wave transmittance of 84% or less at a frequency of 100 GHz when converted into a glass plate having a thickness of 18 mm.
4. When a plane wave with a frequency of 10 GHz and an electric field strength of 1 V / m is incident on a glass plate with a thickness of 1.2 λ from a wave source 2 λ away from the aperture, the electric field strength at an observation point 10 λ away from the aperture is y (V / m), and the aperture area S (mm 2 ) to λ 2 The glass plate according to any one of claims 1 to 3, wherein the linear approximation is y>(0.0607×x), where x is the value obtained by dividing by y.
5. The glass plate according to any one of claims 1 to 4, wherein the exponential approximation is y'>exp(-0.081 x'), where y' is an approximate transmittance at a frequency of 100 GHz and x' (mm) is a thickness of the glass plate.
6. The relationship between frequency x'' and radio wave transmittance y'' at frequencies of 6 to 20 GHz, converted to a thickness of 18 mm, is y'' = [constant 1] x e [定数2]×x’’ In the exponential approximation to the function y''>0.8619e -0.015x’’ The glass plate according to any one of claims 1 to 5.
7. The area is 900 mm 2 The glass plate according to any one of claims 1 to 6.
8. The specific gravity is 2.40 to 3.00, the Young's modulus is 60 GPa to 100 GPa, and the average linear expansion coefficient at 50°C to 350°C is 35×10 -7 ~120 x 10 -7 The glass plate according to any one of claims 1 to 7, wherein the temperature is 0.15°C.
9. Na in water resistance test 2 The glass plate according to any one of claims 1 to 8, wherein the amount of O eluted is 0.001 mg to 0.6 mg.
10. T 2 is 1750°C or less, T 4 is 1350°C or less, T 4 -T L The glass plate according to any one of claims 1 to 9, wherein the glass plate has a temperature of -150°C or higher. (However, T 2 The glass viscosity is 10 2 (dPa s), T 4 The glass viscosity is 10 4 (dPa s), T L is the liquidus temperature of glass.)
11. Glass transition temperature T g The glass sheet according to any one of claims 1 to 10, wherein the temperature is from 400°C to 750°C.
12. The glass plate according to any one of claims 1 to 11, having a visible light transmittance Tv_A converted to a plate thickness of 3.85 mm of 30 to 92%.
13. The glass plate according to any one of claims 1 to 12, having a solar transmittance Te converted to a plate thickness of 3.85 mm of 35 to 91%.
14. A x radio wave transmittance is 0.0225m 2 ・%~8400m 2 % where A is the area of the glass plate (m 2 The glass plate according to any one of claims 1 to 13,
15. The glass sheet according to any one of the preceding claims, having a radio wave transmittance / t of 0.7% / mm to 84% / mm, where t is the thickness (mm) of the glass sheet.
16. A window comprising a glass pane according to any one of claims 1 to 15.
17. 17. The window of claim 16, which is for an automobile or a building material.
18. A wireless communication device comprising the glass plate according to any one of claims 1 to 15.
Citation Information
Patent Citations
Transparent glass
JP1996188444A
Ultraviolet ray and infrared ray absorbing glass and method of manufacturing the same
JP2002348143A
Glass with improved toughness and scratch resistance
JP2011505323A
Borosilicate glass
JP2014024731A
Low dielectric glass and fiber glass
JP2017001950A